Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Particle-in-cell simulations of quantum plasmas - Gregory K. Ngirmang; Hue T.B. Do; Guangxin Liu; Michel Bosman; Lin Wu (Computer Physics Communications, 2026)

Biomimetic nanozyme-mediated domino catalysis for reprogramming energy metabolism to enhance ferroptosis against TNBC - Annan Liu; Lei Li; Ze Wang; Kejun Jiang; Hao Liang; Yiying Ding; Andrew K. Whittaker; Quan Lin (Chemical Engineering Journal, 2026)

Effects of Lactobacillus- and Bacillus-based probiotics on growth performance, intestinal barrier function, and microbiota modulation in nursery pigs: A meta-analysis - K. Sahatsanon; A. Jayanegara; S.W. Kim; Y. Ruangpanit; C.-S. Lin; P. Sivapirunthep; C. Chaosap (Animal Feed Science and Technology, 2026)

Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Electron Beam Irradiation Elicits Dose-Dependent Physio-Biochemical Responses and Antioxidant Defense Modulation in Sugarcane (Saccharum spp. hybrid) - Hai-Rong Huang; Kai-Chao Wu; Meng-Ling Weng; Krishan K. Verma; Tian Pang; Ling-Ling Liang; Zhi-Nian Deng; Lin Xu (Sugar Tech, 2026)

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Wild bees occupy temporally stable pollen nutritional niches - Anthony D. Vaudo; Jillian A. Luthy; Eva Lin; Sonja K. Glasser; Anne S. Leonard (Oecologia, 2026)
As bees’ primary source of protein and lipids, pollen is a nutritional resource key to the persistence of wild populations. Because bee taxa may differ in their pollen macronutrient requirements, and pollen is a limited resource that varies chemically across plants, nutritional niches may shape bees’ ecological interactions. To explore whether members of bee communities occupy pollen nutritional niches, we analysed the protein and lipid content of pollen collected by abundant bee subgenera ( Nomadopsis , Melanosmia , Eumelissodes , Pyrobombus ) and observed their pollen-collecting visitation to plant species at a single Sierra Nevada meadow across three years. We compared pollen nutrition and host plant visitation among subgenera, and at the species level within Pyrobombus. Subgenera exhibited clear and temporally consistent separation of pollen load macronutrition each year, achieved by either host-plant fidelity or flexibility when foraging. Pyrobombus species shared a nutritional niche, potentially creating competition for pollen macronutrients among species relieved by their taxonomic flexibility. These results offer some of the first evidence that nutritional niches among wild bee taxa are annually stable and demonstrate how different taxa may forage to achieve nutritional consistency. Relevant to bee conservation, our findings emphasize that a nutritionally diverse array of plants may be required to support wild bee communities.

A coarse-to-fine machine-learning framework for identifying functional connectivity markers of cognitive impairment in Parkinson’s disease - Chung-Yao Chien; Tsung-Lin Lee; Tien-Yu Lin; Rwei-Ling Yu; Chou-Ching K. Lin (Medical & Biological Engineering & Computing, 2026)

PROMETHEUS clinical trial protocol: tailoring healthy ageing with lifestyle and nutraceuticals - Ajla Hodzic Kuerec; Lihuan Guan; Weilan Wang; Duarte Barros; Wejdan M. Alenezi; Jozo Grgic; Vanessa K. Wazny; Jordi Morwani-Mangnani; Mazzarine Dotou; Dingding Zhang; Tong Chen; Jiaqiu Wang; et al. (GeroScience, 2026)
The d emographic shift toward an older population is accelerating the prevalence of age-related diseases. Precision geromedicine represents a paradigm shift in targeting the biological processes of ageing to optimise health and healthspan, which likely requires multimodal tailored interventions. PROMETHEUS, as part of the XPRIZE healthspan semi-finalist competition, is an 8-week feasibility and exploratory study including 20 middle-aged-to-older participants who received a multimodal intervention comprising fundamental and augmented interventions. The fundamental interventions include sleep and dietary recommendations; supplementation with whey protein, creatine, and fucoidan; supervised exercise with an exergaming component (dual-task cognitive-physical training); motivational interviewing; and cognitive behavioural therapy. The augmented intervention is further personalised based on predefined gerotypes, reflecting individual ageing patterns beyond chronological age. At baseline, urolithin A, nicotinamide mononucleotide, and/or multivitamin-multimineral were prescribed to participants based on their muscle mass, VO 2 peak, and cognitive performance. At mid-intervention, interventions were adjusted based on individual response, including dose escalation and/or the addition of ergothioneine for inadequate improvement in cognition. Primary outcomes include measures of muscle strength and mass, immune function and cognitive performance, and feasibility indicators such as adherence and trial completion. Secondary outcomes include assessments of other biological, clinical, and digital biomarkers of ageing, as well as qualitative indicators of motivation and personal values. This study is aimed at investigating the recruitment feasibility, safety, adherence, and exploratory outcome trajectories of a multimodal, personalised precision geromedicine intervention protocol based on individual participant’s baseline characteristics and interim responses. These findings will also inform the design of a subsequent 12-month, randomised controlled trial evaluating personalised lifestyle and nutraceutical strategies with the potential to incorporate repurposed pharmacological agents to optimise age-related health outcomes.

Correction: The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta‑Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

3-Mercaptopropyltrimethoxysilane combined with manganese sulfate reduces Cd accumulation in wheat on weakly alkaline soils via plant-soil-microorganism regulation - Li Zhang; Nan Zhao; Ajit K Sarmah; Lijie Zhao; Qiang Zeng; Yuepeng La; Dasong Lin; Ruigang Wang (Journal of Environmental Sciences, 2026)

Interrelationships among PM2.5/O3 concentrations, polluted weather patterns, and meteorological conditions over Taiwan based on 2006–2024 observations - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Meng-Hsuan Lee; Ja-Huai Lee; Chih-Chung Chang; Wei-Nai Chen; Chian-Yi Liu (Atmospheric Research, 2026)

Influence of surgical intervention on pre- and post-surgery patient specific muscle synergies in children with cerebral palsy - Tiana Breust; Jiayin Lin; Vincent C. K. Cheung; Firooz Salami; Sebastian I. Wolf; Gursel Alici; Manish Sreenivasa (Experimental Brain Research, 2026)
Muscle synergy analysis has been explored as means to better understand changes in motor control, with the aim to improve treatment outcomes after Single Event Multilevel Surgery (SEMLS) for children with cerebral palsy (CP). In this single-group study, we assess changes between pre- and post-surgery muscle synergies at both patient specific, and cohort levels after surgical intervention for children with CP. We analysed the walking data of 11 patients between the ages of 7–18 years old, including surface electromyography, joint angles and ground reaction forces, recorded before and after surgery. Muscle synergies were extracted and assessed for changes in dimensionality and sparseness between pre- and post-surgery. Our results show that at a patient specific level, pre- and post-surgery muscle synergies were not highly similar, with only 41% of paired synergies showing high correlation ( $$r$$ $$>$$ 0.8) after surgery, and an overall mean correlation of 0.53 $$±$$ 0.25. On the other hand, synergies obtained at the cohort level were highly similar post-surgery ( $$r$$ $$>$$ 0.87). These findings suggest that at an individual level, pre-surgery motor control cannot be assumed to be preserved post-surgery. CP synergies obtained at the cohort level from pre-surgery data can demonstrate more reliable preservation in post-surgery motor control. We also observed sparseness increasing with the number of synergies, which provides an interesting future research direction exploring the link with more complex motor control and a more typical gait pattern.

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Subject-specific whole-lung CFPD coupled with PBPK/PD to predict inhaled bronchodilator response in asthmatic and healthy subjects - Prathish K. Rajaraman; Xuan Zhang; Alejandro P. Comellas; Eric A. Hoffman; Ching-Long Lin (Journal of Aerosol Science, 2026)

A systematic review and meta-analysis comparing the health burden of extreme heat and cold on mortality and urgent care utilization - Zhongguo Huang; Junrong Ma; Randy Tangang; Stephanie K. Zaloom; Wenjun Ma; Xiaobo Xue Romeiko; Shao Lin (International Journal of Hygiene and Environmental Health, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Charge-governed ionic essential oil-loaded liposomes for enhanced penetration and removal of Listeria monocytogenes biofilms - Jinming Dai; Mei Bai; Tariq Aziz; Fatma Alshehri; Nada K. Alharbi; Ashwag Shami; Fakhria A. Al-Joufi; Haiying Cui; Lin Lin (Food Research International, 2026)

Bionanocomposite films constituted by chitosan and ZnO nanoparticles stabilized by tea polyphenols for mango preservation - Jinlong Xu; Xuejie Shi; Minghan Liu; Mantun Gu; Xi Dai; Tariq Aziz; Nada K. Alharbi; Mariam Ameen Mojally; Fahad Al-Asmari; Fakhria A. Al-Joufi; Lin Lin (Food Hydrocolloids, 2026)

Metabolomic and physiological responses of mulberry plants to exogenous molybdenum enhance amino acid and sugar metabolism - Zipei Cui; Michael Ackah; Frank Kwarteng Amoako; Jianbin Li; Aaron Tettey Asare; Changyu Qiu; Qiang Lin; Owuraku Amponsah Abu; Isaac K. A. Galyuon; Xueying Jin; Mengdi Zhao; Weiguo Zhao (Plant and Soil, 2026)

Pliocene otoliths from NW India reveal first fossil osphronemid and structure of a Himalayan freshwater ecosystem - Ningthoujam Premjit Singh; Chien-Hsiang Lin; Ramesh Kumar Sehgal; Abhishek Pratap Singh; Konsam Nildy Devi; Rigzen Angmo; Haroon Nazir; Rajeev Patnaik; K. Milankumar Sharma (Palaeobiodiversity and Palaeoenvironments, 2026)
The Neogene Siwalik deposits have long been recognised for their rich terrestrial fossil record, yet their freshwater ichthyofauna remains virtually unknown. This gap limits our understanding of past aquatic ecosystems and the biogeographic history of South Asian freshwater fishes. In this study, we report the first fossil record of freshwater fish otoliths from the Upper Siwalik Pliocene deposits of Mohand, Saharanpur district, in the northwestern Himalaya, India. Three taxa Channa (Channidae), Trichogaster fasciata (Osphronemidae), and Gobiidae indet. were discovered through our extensive bulk sampling. Among these, T. fasciata represents the second known fossil record of Osphronemidae globally and the first based on otoliths. The assemblage reflects a structured trophic composition composed of mid-level preys and apex predators. These faunal components suggest a calm, possibly lentic freshwater habitat with dense vegetation, consistent with the spawning behaviour of labyrinth fishes and the hunting of snakeheads. Despite the limited number of otoliths, this collection provides rare but significant insights into Pliocene freshwater biodiversity in the Himalayan region.

Boosting ammonia-fed solid oxide fuel cell performance via high-entropy alloy anode surface modification - Nasima Khatun; Cheng-Ju Lin; Jia-You Lin; Sridharan Balu; Shi-Shin Yang; Sea-Fue Wang; Thomas C.-K. Yang (Fuel, 2026)

Electrospinning of gelatin-based composite Nanofibrous coating loaded with Citral and its antibacterial application in chilled meat preservation - Jinming Dai; Mei Bai; Tariq Aziz; Nada K. Alharbi; Ashwag Shami; Fahad Al-Asmari; Fakhria A. Al-Joufi; Haiying Cui; Lin Lin (Food Research International, 2026)

Correction: Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Development of a Stereolithography 3D Printing-Based Micropatterning Method to Study Endothelial-to-Mesenchymal Transition Mechanobiology - Karina Bender; Sarah Chesley; Jay Lesny Drake; Megan Ho; Emily Lin; Kathryn Saxton; Ninava Sharma; Christina K. Tripsas; Qian Li; Jeffrey J. Hsu (Annals of Biomedical Engineering, 2026)
Endothelial-to-mesenchymal transition (EndMT) is the process of endothelial cells undergoing molecular changes that shift their phenotype from that of endothelial cells to that of mesenchymal-like cells. It is a crucial developmental process that has been implicated in various physiological and pathological conditions. EndMT has gained attention as a potential therapeutic target for cardiovascular disease processes, including atherosclerosis, myocardial fibrosis, and vascular calcification. In addition to the assessment of endothelial and mesenchymal markers, the behavioral mechanics of endothelial cells, such as migration and invasion, are often used to identify endothelial cells that have undergone EndMT. However, whether cell chirality may be another mechanobiological marker of EndMT remains unclear. In this study, we aimed to develop an accessible micropatterning platform and created a stereolithography (SLA) 3D printing-based polydimethylsiloxane (PDMS) protein-stamp fabrication platform to create customized patterns of ECM proteins to study endothelial cell chirality during EndMT. Human aortic endothelial cells (HAECs) were treated with the inflammatory cytokine tumor necrosis factor-α (TNF-α), which resulted in the downregulation of the endothelial marker ENOS3 and the upregulation of the mesenchymal markers N-cadherin and transgelin, supporting the induction of EndMT. HAECs were seeded onto fibronectin stripe micropatterns, and cell chirality was measured using custom cell-profiling software. HAECs treated with TNF-α exhibited a shift in cell orientation by approximately 18°, supporting altered cell chirality during TNF-α-induced EndMT. Our work innovates novel methods of studying EndMT by developing a flexible and cost-effective protein-stamp fabrication and image analysis pipeline. This pipeline can be used by researchers to study the endothelial cell chirality in response to EndMT induction.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Synergistic electron highways and mechanical buffering in a dual-carbon confined MoS2 anode for superior sodium-ion storage - Jiarong Li; Guoquan Suo; Chuanjin Lin; Juzhen Li; Xuanchi Luo; Guanglong Yang; Laraib Habib; Zhanar K. Kalkozova; Kashif Naseem (Chemical Engineering Journal, 2026)

Feasibility of a Multi-Laboratory Model of Middle Cerebral Artery Thromboembolic Stroke with Thrombolysis: TE-MCAo - Michelle Lin; Mozammel Bhuiyan; Carly McCurry; Jessica Lamb; Marcio A. Diniz; Karni Bedirian; Anil K. Chauhan; Abhishek Jha; Aditi Jain; Enrique C. Leira; Rakeshkumar Patel; Mohammad B. Khan; et al. (Translational Stroke Research, 2026)
No single animal stroke model satisfies all needs of translational stroke investigation. While the nylon filament model is widely accepted in preclinical translational stroke research, thromboembolic models have more physiological relevance. Thromboembolic models are technically difficult, time consuming, and show variable results, making them problematic for multi-laboratory preclinical network use. We sought to develop and validate a multi-laboratory thromboembolic middle cerebral artery occlusion model that encompasses vessel occlusion and subsequent thrombolysis. To reduce the numbers of donor animals used, we developed a method to store donor blood for later use. Using prefabricated microcatheters, we simplified thrombus preparation and handling. Emboli were prepared in microcatheters and injected directly into the middle cerebral artery from the internal carotid artery. For thrombolysis we used intravenous Tenecteplase dosing at 1.5 mg/kg. To demonstrate feasibility and ease-of-use, the model was implemented at six research laboratories. We wrote and field-tested standard operating procedures, training videos, and hands-on surgical training workshops. We enrolled 170 Sprague Dawley rats of both sexes at six laboratories who performed 4 to 6 thrombus embolizations per week. All sites could achieve reproducible occlusion and thrombolysis. Thromboemboli prepared from stored blood served as well as emboli from freshly drawn blood. Of 135 rats who received one embolus, 33 (24%) died before 48-hour MRI scan. In survivors, stroke volume was 13 ± 16% of the ipsilateral hemisphere. Occlusions were seen in the MCA in 15%, distal ICA in 19%, both (T-occlusions) in 2% and in the MCA/ACA in 1%. Corner test, neurobehavioral battery, and MRI showed reasonably consistent stroke injury. We established the feasibility and reproducibility of a multi-laboratory rodent thromboembolic model but further development is needed to improve the success rate and lower the mortality rate before this model can be accepted widely.

Resistance of shallow soil carbon to both short-term isolated and recurrent droughts in two semi-arid grasslands - Taofeek O. Muraina; Niwu Te; Saheed O. Jimoh; Robert Griffin-Nolan; Lin Song; Jiaqi Chen; Yuan Shi; Ahmed A. Amisu; Tilak Chaudhary; Qiang Yu; Melinda D. Smith; Alan K. Knapp; et al. (Oecologia, 2026)

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Expansion of Molecular and Clinical Aspects of EPS8L2 (DFNB106)-Associated Hearing Loss Emphasizes a Potential Therapeutic Window - Daniel Owrang; Aboulfazl Rad; Masoome Alerasool; Susanne M. Kolb; Sheng-Jia Lin; Julia Doll; Neda Alidadiani; Shahrooz Ghaderi; Michaela A. H. Hofrichter; Reza Maroofian; Gaurav K. Varshney; Majid Mojarrad; et al. (Molecular Neurobiology, 2026)
EPS8L2, encoding EPS8 signaling adaptor L2 protein, is critical for stereocilia maintenance in cochlear hair cells. Four previously published families have replicated autosomal recessive non-syndromic hearing loss (DFNB106), yet the mutational and clinical spectrum remains poorly described. This study expands the mutational and clinical spectrum of EPS8L2 -associated hearing impairment by identifying five additional individuals in four families, more than doubling the number of reported cases to date, while going deeper into clinical aspects. These include two frameshift variants c.818_827dup, p.(Ala279Glyfs*36) and c.1430dup, p.(Val478Serfs*25), the first nonsense variant c.1878C > A, p.(Tyr626Ter), and the first missense variant with a spliceogenic effect c.767C > G, p.(Thr256Arg). Functional analysis confirmed that the c.767C > G variant causes exon 9 skipping, leading to a frameshift r.701_768del, p.(Gly234Alafs*55). A shared 4.17 Mb homozygous region among two unrelated Iranian families with this variant suggested a founder effect. These individuals uniquely showed U-shaped audiograms as a new association of more severe middle frequency hearing loss. Clinically, affected individuals presented moderate to moderately severe hearing loss that was mostly progressive, with an onset starting between the prelingual stage, extending postlingually. A younger sibling of the first European proband diagnosed with DFNB106 passed newborn hearing screening but was identified with compound heterozygous variants, underscoring the importance of early genetic testing. The progressive nature of EPS8L2 -related hearing loss is unusual for recessive non-syndromic forms and highlights the need for early monitoring and intervention. This work emphasizes the need for early molecular diagnosis and long-term clinical follow-up, while describing the natural history of EPS8L2 that will be important for future therapeutic development.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

A major and stable QTL confers impatiens necrotic spot virus resistance in lettuce cv. Eruption - Santosh Nayak; Kelley L. Richardson; Renée L. Eriksen; Daniel K. Hasegawa; William M. Wintermantel; Manoj Sapkota; Xuemei Tang; Shufen Chen; Meng Lin; Dongyan Zhao; Craig T. Beil; Moira J. Sheehan; et al. (Theoretical and Applied Genetics, 2025)
Key message A large effect and environmentally stable QTL was identified on LG2 that confers high levels of INSV resistance in lettuce cultivar Eruption. Abstract Impatiens necrotic spot virus (INSV) has recently emerged as a major threat to lettuce production in the Salinas Valley of California, the region which contributes over 60% of the US national supply. This thrips-transmitted virus can infect lettuce plants at any growth stage, causing premature death or a total loss of marketability. Both INSV and its thrips vector have broad host ranges, which complicate disease management. Utilizing genetic resistance is the most sustainable approach; however, complete immunity has not been identified and the genetic basis of resistance to INSV in lettuce remains poorly understood. This study aimed to identify quantitative trait loci (QTL) and elucidate the underlying mechanism of INSV resistance in ‘Eruption,’ a lettuce cultivar exhibiting highly stable partial resistance across environments. Using 162 F 6:8 recombinant inbred lines (RILs) developed from a cross between moderately susceptible ‘Reine des Glaces’ and ‘Eruption,’ and a genetic linkage map comprising 1598 single nucleotide polymorphism (SNP) markers, phenotypic data collected from field and greenhouse experiments consistently revealed a highly significant, major QTL on linkage group 2. This QTL exhibited partial dominance with additive effects, explaining up to 61% of the total phenotypic variation for INSV disease severity. Furthermore, INSV resistance was found to be highly heritable, with heritability estimates of up to 0.89, indicating strong genetic control. Results of this study are crucial for fine mapping and the development of marker-assisted selection assays to accelerate the breeding of more advanced INSV-resistant lettuce cultivars.

Early Cenozoic source to sink relation between the Tula Basin and the surrounding ranges: Insights for the Tibetan Plateau growth - Jingzhen Peng; Feng Cheng; Dehai Zhang; Hongwei Zhou; Maomao Wang; Xiangzhong Li; Zhaojie Guo; A. K. Khudoley; A. S. Tesakov; Lin Wang; Yan Ma (Science China Earth Sciences, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Walruses are potentially exposed to paralytic shellfish toxin concentrations that impact their health during Alexandrium blooms in the Alaskan Arctic - Patrick Charapata; Evangeline Fachon; Donald M. Anderson; Gay Sheffield; Emily K. Bowers; Robert S. Pickart; Peigen Lin; Kathi A. Lefebvre (Harmful Algae, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Toxin-responsive Litsea cubeba essential oil liposomes for enhancing beef safety by inhibiting Clostridium perfringens and its exotoxin activity - Xiaochen Chen; Jingjing Wu; Tariq Aziz; Nada K. Alharbi; Ashwag Shami; Fahad Al-Asmari; Fakhria A. Al-Joufi; Abeer M. Alghamdi; Lin Lin (Food Bioscience, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

Evaluation of the asymmetric distribution of Japanese eel recruitment to eastern and western Japan - Yu-Lin K. Chang; Mari Kuroki (Regional Studies in Marine Science, 2025)

Schiff's base crosslinked gelatin-dialdehyde cellulose film with gallic acid for improved water resistance and antimicrobial properties - Myat Noe Khin; Md Easdani; Tariq Aziz; Ashwag Shami; Nada K. Alharbi; Fahad Al-Asmari; Lin Lin (Food Hydrocolloids, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Saxitoxin Linked to Deaths of Northern Fur Seals in the Southeast Bering Sea - Kathi A. Lefebvre; Chelsea M. Campbell; Lauren M. Divine; Paul Melovidov; Hanna Hellen; Kathy Burek Huntington; Emily K. Bowers; Natalie Rouse; Evangeline Fachon; Thomas J. Farrugia; Robert S. Pickart; Peigen Lin; et al. (Marine Mammal Science, 2025)
In August 2024, a northern fur seal mortality event was observed on St. Paul Island, AK in the southeast (SE) Bering Sea. Ten seals in good body condition were found dead along with large accumulations of dead fish on Benson Beach located on St. Paul Island. Full necropsies of the five available adult seals, one pup, and several fish did not reveal any overt causes of death. Testing of tissues for the algal neurotoxins domoic acid (DA) and saxitoxin (STX) confirmed the presence of STX in multiple tissues and physiological exposure in all five adult NFS and the two fish available for testing. DA was not detected in any samples. Complimentary samples of the SE Bering Sea ecosystem during the same time frame and location as the die off revealed bloom densities of Alexandrium catenella (the dinoflagellate that produces STX), large A. catenella cyst beds, and high prevalences of STX in fish (100%, n = 22), zooplankton (93%, n = 28), clams (100%, n = 10) and worms (93% n = 15) in the foraging area of NFS. High STX concentrations were observed in fish, clams, worms, and NFS urine, providing compelling evidence for a STX poisoning event.

A novel adsorbent for efficient metal recovery from aqueous solutions: Carbon-coated oil-treated plastic granules as a sustainable approach to resource conservation - Farideh Pahlavan; Harpreet Kaur; Hamed Khodadaditirkolaei; Sk Faisal Kabir; Jung-Ying Lin; Laura K. G. Ackerman-Biegasiewicz; Elham H. Fini (Resources, Conservation and Recycling, 2025)

Nitrogen-doped hierarchical porous carbon derived from shea nut shell for high-performance supercapacitor and LiS battery - Daniel Nframah Ampong; Wang Lin; Felipe M. de Souza; Frank Ofori Agyemang; Anthony Andrews; Kwadwo Mensah-Darkwa; Ram K. Gupta (Next Research, 2025)

Speciation of coral-associated barnacles: generalists versus specialists in the Indo-West Pacific - Hsiu-Chin Lin; Lorenzo C. Halasan; Yoko Nozawa; Benny K. K. Chan (Coral Reefs, 2025)

Attachment performance between micro particles and different sized aerobic granular sludge - from outside to inside - Zhaoxu Peng; Yuemei Lin; Mark C.M. van Loosdrecht; Merle K. de Kreuk (Water Research, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Revealing considerable emissions reduction potential in flight operations: A real-time emission perspective - Simeng Ma; Shizhuo Lin; Bo Han; Chen Zhang; Zhiqiang Wei; Lingxiang Xue; Jingbo Zhao; Kun Wang; Jian Yu; Philip K. Hopke (Transportation Research Part D: Transport and Environment, 2025)

Influence of infant feeding practices on childhood dietary patterns in Upstate KIDS - Priscilla K. Clayton; Diane L. Putnick; Tzu-Chun Lin; Edwina H. Yeung (Appetite, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Real and long-time predicting the trajectories of internal solitary waves: Case studies in the Sulu Sea - Longyu Huang; Jingsong Yang; Lin Ren; Zetai Ma; Yu Chai; Peng Chen; Shuangyan He; Bingqing Liu; Antony K. Liu (Ocean Engineering, 2025)

The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta-Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2025)
A large number of drugs and compounds produced by the chemical and agrochemical industry, often referred to as ‘non-genotoxic carcinogens’ (NGC), score as tumour promotors in rodent models. It is unclear whether these compounds act similarly in humans. The most extensively investigated compounds have been the anti-convulsive drugs, phenobarbital (PB), and phenytoin. Liver tumours induced by PB are dependent upon the activation of the constitutive androstane receptor (CAR). However, marked species differences in CAR activation by exogenous chemicals exist with some being much more potent activators of human CAR, e.g., 6-(4-chlorophenyl)imidazo[2,1-β][1,3]thiazole-5-carbaldehyde-O-(3,4-dichlorobenzyl)oxime (CITCO). We have compared CITCO-induced tumour formation in the livers of mice in which murine CAR has been replaced with its human counterpart. Our findings reveal that CITCO-dependent liver tumours are only formed in mice-expressing human CAR and not in wild-type animals. In addition, contrary to one of the proposed mechanisms of NGC carcinogenicity, we show that CITCO did not induce a hyperplastic response in the liver of the humanised mice. These data raise some key questions about the mechanism of action of NGCs and identify the limitations of current rodent carcinogenicity test systems in relation to risk assessment.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Fered-Fenton enhanced boron-doped diamond electrochemical oxidation for wastewater treatment: Antibiotic degradation, kinetics, and environmental effects - C. Chokejaroenrat; K. Poomipuen; K. Techauay; P. Weaoseng; U. Jermnak; H. Chokthaweepanich; N. Suriyachai; Y.-T. Lin; K. Imsilp; C. Sakulthaew (Journal of Water Process Engineering, 2025)

Restorative effects of highway roadside urban forests: A simulated approach - Qunyue Liu; Kunneng Jiang; Ziming Wang; Yumeng Wang; Huiting Zhang; Qingju Wang; Hangqing Chen; Donghuang Lin; Ulrika K. Stigsdotter; Yuxiang Lan (Forest Policy and Economics, 2025)

A long-period assessment of climate change impact on river water quality in the central region of Iran - M. Moazeni; M. Sayedipour; K. Y. A. Lin; A. Ebrahimi (International Journal of Environmental Science and Technology, 2025)

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

Cubic calcite and its structural phase transitions - Yang Yang; Yixin Lin; Xiangdong Ding; Christopher J. Howard; Ekhard K. H. Salje (Physics and Chemistry of Minerals, 2025)
Calcite, CaCO 3 , has been reported to exist in as many as seven different structural forms. The structure at room temperature and pressure (space group R $$\overline{3 }$$ 3 ¯ c , ‘Phase I’) was established by Bragg many years ago. A phase transition to a higher temperature phase (space group R $$\overline{3 }$$ 3 ¯ m, ‘Phase V’) was noted to occur at around 1240 K—this may proceed via an intermediate phase (space group again R $$\overline{3 }$$ 3 ¯ c , referred to as ‘Phase IV’). These phases differ primarily in the disposition of the CO 3 groups. Additional phases are found at higher pressures. We report a para-phase (parent phase, virtual prototype, aristotype) which assists in understanding the different phases, the phase transitions, and especially the domain structures and twin wall boundaries associated with these transitions. Molecular dynamics methods were used to study the temperature evolution of an isothermal-isobaric (NPT) ensemble of some 384,000 atoms. These computations reproduced the features of the known structures in R $$\overline{3 }$$ 3 ¯ c and R $$\overline{3 }$$ 3 ¯ m and then, at higher temperature, revealed a structure of the sodium chloride type (space group Fm $$\overline{3 }$$ 3 ¯ m ) in which the entities were the Ca 2+ cation and the CO 3 2− anion, this latter with effectively spherical symmetry. On this basis we have upon cooling a necessarily first order ferroelastic transition from cubic Fm $$\overline{3 }$$ 3 ¯ m to rhombohedral R $$\overline{3 }$$ 3 ¯ m , computed to occur at a simulated temperature of 1900 K, and a possibly continuous transition from the R $$\overline{3 }$$ 3 ¯ m to rhombohedral (on a doubled cell) R $$\overline{3 }$$ 3 ¯ c computed to occur at about 1525 K. The computations also allowed us to follow the domain structure and twin walls as a function of temperature, during both heating and cooling. The structure just below the R $$\overline{3 }$$ 3 ¯ m to R $$\overline{3 }$$ 3 ¯ c transition shows strong disorder in the orientation of the CO 3 groups, and this may be what is sometimes referred to as Phase IV. The domain structure just below the cubic to rhombohedral transition shows twinning of typical ferroelastic character. The doubling of the cell below the R $$\overline{3 }$$ 3 ¯ m to rhombohedral (on a doubled cell) R $$\overline{3 }$$ 3 ¯ c leads to a more complicated twin pattern. Indeed, the different structures can be identified from patterns of twinning. Differences between domain structures obtained on heating and cooling indicate extensive thermal metastabilities.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Source specific fine particles and rates of asthma and COPD healthcare encounters pre- and post-implementation of the Tier 3 vehicle emissions control regulations - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; Philip K. Hopke; David Q. Rich (Journal of Hazardous Materials, 2025)

Full-scale testing and monitoring of geosynthetics-stabilized flexible pavement in Alberta, Canada - Mian Huang; Jiming Liu; Sanat K. Pokharel; Taylor Dagenais; Arghya Chatterjee; Cheng Lin (Geotextiles and Geomembranes, 2025)

Freeze-thaw impacts on geocell-stabilized bases considering effects of water supply and compaction - Mian Huang; Sanat K. Pokharel; Minghao Liu; Cheng Lin (Geotextiles and Geomembranes, 2025)

Food additives as photosensitizers: A systematic review and narrative synthesis - Wanzhen Dai; Jiamiao Hu; Bee K. Tan; Shaoling Lin (Food Chemistry, 2025)

Unraveling the complexities of ozone and PM2.5 pollution in the Pearl River Delta region: Impacts of precursors emissions and meteorological factors, and effective mitigation strategies - Yating Chen; Liye Zhu; Sihui Wang; Daven K. Henze; Tzung-May Fu; Lin Zhang; Xiaoling Wang (Atmospheric Pollution Research, 2025)

Impacts of blending advanced treated water and traditional groundwater supply on lead and copper concentrations and microbial diversity in premise plumbing - Anushka Mishrra; Lin Zhang; Janelle Junior; Fangqiong Ling; Nicole K. Blute; Daniel E. Giammar (Water Research, 2025)

Epigenetic modifications control CYP1A1 Inducibility in human and rat keratinocytes - Lo-Wei Lin; Allison K. Ehrlich; Robert H. Rice (Toxicology and Applied Pharmacology, 2025)

Evaluation of pollution potential in swine manure across growth stages: Impact of dietary nutrients and management strategies - Hongyong Fan; Chenghao Li; Wenxuan Zhang; Chaoxiang Liu; Olusegun K. Abass; Lin Liu; Xu Huang; Yingjie Sun; Huawei Wang; Maureen W. Gesiye; Wushan Chen (Science of The Total Environment, 2025)

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Northern shifts in the migration of Japanese glass eels to subarctic Hokkaido Island over the past three decades - Yu-Lin K. Chang; Kentaro Morita; Kanta Muramatsu; Osamu Kishida; Mari Kuroki (Ocean Dynamics, 2025)

Dietary protein restriction diminishes sucrose reward and reduces sucrose-evoked mesolimbic dopamine signaling in mice - Chih-Ting Wu; Diego Gonzalez Magaña; Jacob Roshgadol; Lin Tian; Karen K. Ryan (Appetite, 2024)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Evaluating thermal sensation in outdoor environments - Different methods of coupling CFD and radiation modelling with a human body thermoregulation model - Dharmasastha K; Haobin Liang; Junwei Lin; Yongxin Xie; Yichen Yu; Jian-lei Niu (Building and Environment, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

Fine mapping of a major co-localized QTL associated with self-incompatibility identified in two F2 populations (broccoli × cauliflower and cauliflower × Chinese kale) - Yusen Shen; Jiansheng Wang; Xiaoguang Sheng; Huifang Yu; Ranjan K. Shaw; Mengfei Song; Shiyi Cai; Shuting Qiao; Fan Lin; Honghui Gu (Theoretical and Applied Genetics, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Soil nitrous oxide emissions from wheat-based rotations with different types of pulse crops - K. Liu; P.V.F. Machado; S. Lin; C.F. Drury; R.L. Lemke (Journal of Environmental Management, 2024)

Short term air pollution exposure during pregnancy and associations with maternal immune markers - C.S. Yount; K. Scheible; S.W. Thurston; X. Qiu; Y. Ge; P.K. Hopke; Y. Lin; R.K. Miller; S.K. Murphy; J. Brunner; E. Barrett; T.G. O'Connor; et al. (Environmental Research, 2024)

PM2.5 and its components and respiratory disease healthcare encounters – Unanticipated increased exposure-response relationships in recent years after environmental policies - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Philip K. Hopke; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; David Q. Rich (Environmental Pollution, 2024)

Structure and transport properties of FeS at planetary core conditions - E. Edmund; T. Bi; Z.M. Geballe; K. Brugman; J.-F. Lin; S. Chariton; V.B. Prakapenka; J. Minár; R.E. Cohen; A.F. Goncharov (Earth and Planetary Science Letters, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

A methodology for gene level omics-WAS integration identifies genes influencing traits associated with cardiovascular risks: the Long Life Family Study - Sandeep Acharya; Shu Liao; Wooseok J. Jung; Yu S. Kang; Vaha Akbary Moghaddam; Mary F. Feitosa; Mary K. Wojczynski; Shiow Lin; Jason A. Anema; Karen Schwander; Jeff O. Connell; Michael A. Province; et al. (Human Genetics, 2024)
The Long Life Family Study (LLFS) enrolled 4953 participants in 539 pedigrees displaying exceptional longevity. To identify genetic mechanisms that affect cardiovascular risks in the LLFS population, we developed a multi-omics integration pipeline and applied it to 11 traits associated with cardiovascular risks. Using our pipeline, we aggregated gene-level statistics from rare-variant analysis, GWAS, and gene expression-trait association by Correlated Meta-Analysis (CMA). Across all traits, CMA identified 64 significant genes after Bonferroni correction (p ≤ 2.8 × 10 –7 ), 29 of which replicated in the Framingham Heart Study (FHS) cohort. Notably, 20 of the 29 replicated genes do not have a previously known trait-associated variant in the GWAS Catalog within 50 kb. Thirteen modules in Protein–Protein Interaction (PPI) networks are significantly enriched in genes with low meta-analysis p-values for at least one trait, three of which are replicated in the FHS cohort. The functional annotation of genes in these modules showed a significant over-representation of trait-related biological processes including sterol transport, protein-lipid complex remodeling, and immune response regulation. Among major findings, our results suggest a role of triglyceride-associated and mast-cell functional genes FCER1A , MS4A2 , GATA2 , HDC , and HRH4 in atherosclerosis risks. Our findings also suggest that lower expression of ATG2A , a gene we found to be associated with BMI, may be both a cause and consequence of obesity. Finally, our results suggest that ENPP3 may play an intermediary role in triglyceride-induced inflammation. Our pipeline is freely available and implemented in the Nextflow workflow language, making it easily runnable on any compute platform ( https://nf-co.re/omicsgenetraitassociation ) .

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Review on personal protective equipment: Emerging concerns in micro(nano)plastic pollution and strategies for addressing environmental challenges - Van-Giang Le; Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Tri Quang Hung Nguyen; Nguyen K. Hue; Quoc-Minh Truong; Soon W. Chang; X. Hoan Nguyen; D. Duc Nguyen (Environmental Research, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

The role of perceived negative partner behavior in daily snacking behavior: A dynamical systems approach - Jingrun Lin; Jennifer K. MacCormack; Steven M. Boker; James A. Coan; Sarah C.E. Stanton (Appetite, 2024)

Experimental investigation into coal wettability changes caused by reactions with scCO2-H2O - Ke Li; Chuanjie Zhu; Jiamin Wan; Tetsu K. Tokunaga; Na Liu; Cong Ma; Baiquan Lin (Gas Science and Engineering, 2024)

Nanoneedles like FeP engineered on Ni-Foam as an effective catalyst towards overall alkaline freshwater, urea, and seawater splitting - Anjali Gupta; Cassia A. Allison; Rishabh Srivastava; Anuj Kumar; Mina Sim; Jeffery Horinek; Wang Lin; Felipe M. de Souza; Sanjay R. Mishra; Felio Perez; Ram K. Gupta; Tim Dawsey (Fuel, 2024)

Utilization of shea butter waste-derived hierarchical activated carbon for high-performance supercapacitor applications - Daniel Nframah Ampong; Wang Lin; Felipe M. de Souza; Vikram Kishore Bharti; Frank Ofori Agyemang; Anthony Andrews; Kwadwo Mensah-Darkwa; Alisha Dhakal; Sanjay R. Mishra; Felio Perez; Ram K. Gupta (Bioresource Technology, 2024)

Formation of secondary aerosol by 222 nm Far-UVC irradiation on SO2 - Zhancong Liang; Liyuan Zhou; Kunpeng Chen; Ying-Hsuan Lin; Alvin C.K. Lai; Patrick K.H. Lee; Patrick H.L. Sit; Ran Yin; Chak K. Chan (Atmospheric Environment, 2024)

Research Overview on Sugarcane Deep Processing and Comprehensive Utilization in China - Gan-Lin Chen; Jing Chen; Bo Lin; Ling-Zhi Zhao; Feng-Jin Zheng; Krishan K. Verma; Yang-Rui Li (Sugar Tech, 2024)

The Effect of Lens Shape, Zonular Insertion and Finite Element Model on Simulated Shape Change of the Eye Lens - Lin Ye; Kehao Wang; Jorge Grasa; Barbara K. Pierscionek (Annals of Biomedical Engineering, 2024)
The process of lens shape change in the eye to alter focussing (accommodation) is still not fully understood. Modelling approaches have been used to complement experimental findings in order to determine how constituents in the accommodative process influence the shape change of the lens. An unexplored factor in modelling is the role of the modelling software on the results of simulated shape change. Finite element models were constructed in both Abaqus and Ansys software using biological parameters from measurements of shape and refractive index of two 35-year-old lenses. The effect of zonular insertion on simulated shape change was tested on both 35-year-old lens models and with both types of software. Comparative analysis of shape change, optical power, and stress distributions showed that lens shape and zonular insertion positions affect the results of simulated shape change and that Abaqus and Ansys show differences in their respective models. The effect of the software package used needs to be taken into account when constructing finite element models and deriving conclusions.

Reconstruction of seamless harmonized Landsat Sentinel-2 (HLS) time series via self-supervised learning - Hao Liu; Hankui K. Zhang; Bo Huang; Lin Yan; Khuong K. Tran; Yuean Qiu; Xiaoyang Zhang; David P. Roy (Remote Sensing of Environment, 2024)

Generation of diurnal internal solitary waves (ISW-D) in the Sulu Sea: From geostationary orbit satellites and numerical simulations - Longyu Huang; Jingsong Yang; Zetai Ma; Bingqing Liu; Lin Ren; Antony K. Liu; Peng Chen (Progress in Oceanography, 2024)

Uranium-series and strontium isotope systematics in soil carbonates from dryland Critical Zones: Implications for soil inorganic carbon storage and transformation - Syprose K. Nyachoti; Victor H. Garcia; Curtis Monger; Craig Tweedie; Thomas E. Gill; Lixin Jin; Lin Ma (Geochimica et Cosmochimica Acta, 2024)

Upcycling of waste polycarbonate to recyclable Poly(carbonate-imines) with exceptional thermal properties and unprecedented flame retardancy - Yi-Chun Chen; Pin-Qi Mu; Kamani Sudhir K. Reddy; Ru-Jong Jeng; Mahdi M. Abu-Omar; Ching-Hsuan Lin (Chemical Engineering Journal, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Potential application of Ginkgo biloba extract as a green corrosion inhibitor for carbon steel reinforcement in chloride-polluted simulated concrete pore solution - Ambrish Singh; K.R. Ansari; Siham K. AbdelRahim; Ismat H. Ali; Brahim EL Ibrahimi; Abdullah K. Alanazi; Muhammad Younas; Yuanhua Lin (Process Safety and Environmental Protection, 2024)

Enhanced detection of heavy metal ions using Ag nanoparticles and single-walled carbon nanotubes within Cu-based metal-organic frameworks - Gajanan A. Bodkhe; Mayuri S. More; Ahmad Umar; Ahmed A. Ibrahim; Subramanian Siva; Megha A. Deshmukh; Nikesh N. Ingle; Dhammajyot K. Gaikwad; Meng-Lin Tsai; Tibor Hianik; Myunghee Kim; Mahendra D. Shirsat (Journal of Environmental Chemical Engineering, 2024)

An ensemble-based data assimilation system for forecasting variability of the Northwestern Pacific ocean - Yasumasa Miyazawa; Max Yaremchuk; Sergey M. Varlamov; Toru Miyama; Yu-Lin K. Chang; Hakase Hayashida (Ocean Dynamics, 2024)
An adjoint-free four-dimensional variational (a4dVar) data assimilation (DA) is implemented in an operational ocean forecast system based on an eddy-resolving ocean general circulation model for the Northwestern Pacific. Validation of the system against independent observations demonstrates that fitting the model to time-dependent satellite altimetry during a 10-day DA window leads to substantial skill improvements in the succeeding 60-day hindcast. The a4dVar corrects representation of the Kuroshio path variation south of Japan by adjusting the dynamical balance between amplitude/wavelength of the meander and flow advection. A larger ensemble spread tends to reduce the skill in representing the observed sea surface height anomaly, suggesting that it is possible to use the ensemble information for quantifying the forecast error. The ensemble information is also utilized for modification of the background error covariance (BEC), which improves the accuracy of temperature and salinity distributions. The modified BEC yields the skill decline of the Kuroshio path variation during the 60-day hindcast period, and the ensemble sensitivity analysis shows that changes in the dynamical balance caused by the ensemble BEC result in such skill deterioration.

Future changes in intense tropical cyclone hazards in the Pearl River Delta region: an air-wave-ocean coupled model study - Zhenning Li; Jimmy C. H. Fung; Mau Fung Wong; Shangfei Lin; Fenying Cai; Wenfeng Lai; Alexis K. H. Lau (Natural Hazards, 2024)
The Pearl River Delta (PRD) region is highly vulnerable to tropical cyclone (TC)-caused coastal hazards due to its long and meandering shoreline and well-developed economy. With global warming expected to continue or worsen in the rest of the twenty-first century, this study examines the TC impact on the PRD coastal regions by reproducing three intense landfalling TCs, namely Vicente (2012), Hato (2017), Mangkhut (2018), using a sophisticated air-wave-ocean coupled model of high spatial resolution (1-km atmosphere and 500-m wave and ocean). The simulations are conducted using present-day reanalysis data and the same TCs occurring in a pseudo-global warming scenario projected for the 2090s. Results indicate that the coupled model accurately reproduces the air-wave-ocean status during the TC episodes. The 2090s thermodynamic status effectively increases the intensity of intense TCs, leading to more severe coastal hazards including gale, rainstorm, and storm surges and waves. On average, the maximum surface wind speed within 50–200 km to the right of the TC center can increase by 4.3 m/s (+22%). The 99th and the 99.9th percentile of accumulated rainfall will increase from 405 to 475 mm (+17.3%), and from 619 to 735 mm (+18.6%), respectively. The maximum significant wave height at the ocean is lifted by an average of 57 cm (+13.8%), and the coastline typically faces a 40–80 cm increase. The maximum storm surges are lifted by 30–80 cm over the open sea but aggravate much higher along the coastline, especially for narrowing estuaries. For Typhoon Vicente (2012), there is more than a 200 cm wave height increase observed both at open sea and along the coastline. In the 2090s context, a combination of mean sea level rise, storm surge, and wave height can reach more than 300 cm increase in total water level at certain hot-spot coastlines, without considering the superposition of spring tides.

Marine macro-litter sources and ecological impact: a review - Van-Giang Le; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Nguyen T. Quang Hung; Akhil P. Khedulkar; Nguyen K. Hue; Phung T. Thu Trang; Arvind Kumar Mungray; D. Duc Nguyen (Environmental Chemistry Letters, 2024)

Life cycle assessment and techno-economic analysis of sustainable bioenergy production: a review - Ahmed I. Osman; Bingbing Fang; Yubing Zhang; Yunfei Liu; Jiacheng Yu; Mohamed Farghali; Ahmed K. Rashwan; Zhonghao Chen; Lin Chen; Ikko Ihara; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2024)
The global expansion of the bioenergy industry raises concerns, emphasizing the need for careful evaluation and sustainable management. To facilitate this, life cycle assessments beyond greenhouse gas emissions and energy balance are essential, along with the standardization of assessment methodologies to enable meaningful comparisons. Here, we review life cycle assessment, chemical aspects, and policy implication of bioenergy production. We discuss life cycle assessment in terms of concepts, methods, impacts, greenhouse gases, land use, water consumption, bioethanol, biodiesel, biogas, and techno-economic analysis. Chemical aspects comprise reaction processes and means to improve efficiency. Concerning policies, tools, and frameworks that encourage sustainable energy production are presented. We found that carbon dioxide removal ranges from 45 to 99% in various bioenergy processes. The review also emphasizes the importance of chemistry in advancing sustainable bioenergy production for a more sustainable and secure energy future.

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Sight and blindness: The relationship between ostracod eyes, water depth, and light availability in the Arctic Ocean - Jingwen Zhang; Moriaki Yasuhara; Chih‐Lin Wei; Skye Yunshu Tian; Kyawt K. T. Aye; Laura Gemery; Thomas M. Cronin; Peter Frenzel; David J. Horne (Limnology and Oceanography, 2024)
Eye loss has been a long‐standing interest in evolutionary biology. Many organisms that inhabit environments without light penetration, for example the deep sea, exhibit eye loss and thus become blind. However, water‐depth distribution of eyes in marine organisms is poorly understood. Ostracods are widely distributed crustaceans, and many sighted marine ostracods have eye tubercles (lenses) on their shells. Since eye tubercles are visible on the shells illustrated in much literature, it is easy to determine their presence or absence via a literature survey. Here, we used a large Arctic‐wide ostracod census dataset (Arctic Ostracode Database) to calculate the eye index (the percentage of species with eyes), and compare them with water depth and light availability. As water depth increases, eye index values decrease and become constantly zero in water deeper than 1000 m. Similar decline of sighted species with increasing depth is also known in isopods and amphipods, suggesting that it may be common in other crustaceans and perhaps in deep‐sea organisms in general. We also show that eye index values increase as light availability increases. This study is the first to quantify how distributions of sighted and blind species change with light availability, giving baseline information on vision in the deep sea.

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

The food matrix properties influence the antibacterial effectiveness of photodynamic and sonodynamic treatments - Shaoling Lin; Jiawen Zhang; Dov Stekel; Yuan Shi; Haoqing Yang; JinBiao Gao; Bee K. Tan; Jiamiao Hu (Innovative Food Science & Emerging Technologies, 2024)

Characteristics and impacts of fine particulates from the largest power plant plume in Taiwan - Ming-Tung Chuang; Charles C.-K Chou; Chung-Te Lee; Ja-Huai Lee; Wei-Che Lin; Chuan-Yao Lin; Wei-Nai Chen; Yi-Ying Chen; Kai-Hsien Chi (Atmospheric Pollution Research, 2024)

Observing glacial isostatic adjustment by PSInSAR in southern Hudson Bay - Chong-You Wang; Yunung Nina Lin; Cheinway Hwang; C K Shum (Remote Sensing of Environment, 2024)

Di-n-butyl phthalate promotes the neural differentiation of mouse embryonic stem cells through neurogenic differentiation 1 - Ying-Chu Lin; Kenly Wuputra; Kohsuke Kato; Chia-Chen Ku; Shigeo Saito; Michiya Noguchi; Yukio Nakamura; Michael Hsiao; Chang-Shen Lin; Deng-Chyang Wu; Atsushi Kawaguchi; Hsin-Su Yu; et al. (Environmental Pollution, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Telomere dynamics during hibernation in a tropical primate - M. B. Blanco; D. L. Smith; L. K. Greene; A. D. Yoder; E. E. Ehmke; J. Lin; P. H. Klopfer (Journal of Comparative Physiology B, 2024)

Advancing ecological assessment of the Arabian Gulf through eDNA metabarcoding: opportunities, prospects, and challenges - Thadickal V. Joydas; Seerangan Manokaran; Jayanath Gopi; Jayachandran P. Rajakumar; Lin Yu-Jia; Moritz Heinle; Mazen K. Nazal; Karuppasamy P. Manikandan; Maryam Qashqari; Sowmya P. Mohandas; Syed A. Hussain; Rommel H. Maneja; et al. (Frontiers in Marine Science, 2024)
The Arabian Gulf (hereafter ‘the Gulf’) is renowned for its unique ecological characteristics and distinct marine life. It offers a diverse range of ecosystems that have adapted to the impacts posed by natural stress and human activities. Regular biomonitoring and diversity assessments are necessary to document the health of the Gulf ecosystem and to implement appropriate measures for effective conservation and management. Recently, environmental DNA (eDNA), a total pool of DNA isolated from environmental samples, has emerged as a highly effective tool for ecological studies. This review explores the opportunities, prospects, and challenges associated with employing eDNA metabarcoding in the ecological assessment and biomonitoring of the Gulf. It provides an overview of the status of the Gulf ecosystem and discusses the potential applications of eDNA metabarcoding in assessing biodiversity, monitoring invasive species, and evaluating ecosystem health. Additionally, the investigation addresses the challenges inherent in implementing this technique, considering environmental complexities, methodological intricacies, and data interpretation. Overall, this review emphasizes the immense potential of eDNA metabarcoding in advancing ecological assessment in the Gulf and calls for further research and collaboration to harness its benefits in this unique marine ecosystem.

Iron nanoparticle coating and plasma-activated water cleaning as a biofouling removal method for reverse osmosis membranes suitable for desalination - Angelina Egorova; Binbin Xia; Heema Kumari Nilesh Vyas; Maria Magdalena Armendáriz-Ontiveros; Yi-Chen Lin; Alejandra Garcia-Garcia; David K. Wang; Patrick J. Cullen; Gustavo Fimbres Weihs; Anne Mai-Prochnow (Journal of Water Process Engineering, 2024)

Resilience of stormwater biofilters following the deposition of wildfire residues: Implication on downstream water quality management in wildfire-prone regions - Onja D. Raoelison; Tonoy K. Das; Keegan Guyett; Rachel Merrifield; Ananya Visweswaran; Shruti Indiresan; Kevin Lin Yang; Gregory Pierce; Sanjay K. Mohanty (Journal of Hazardous Materials, 2024)

RNF4 prevents genomic instability caused by chronic DNA under-replication - Marissa K. Oram; Ryan M. Baxley; Emily M. Simon; Kevin Lin; Ya-Chu Chang; Liangjun Wang; Chad L. Myers; Anja-Katrin Bielinsky (DNA Repair, 2024)

Integrating water and insect pest management in agriculture - Po-An Lin; Sulav Paudel; Pin-Chu Lai; Raj K. GC; Dan-Hong Yang; Gary W. Felton (Journal of Pest Science, 2024)

Anthropogenic emission controls organic aerosols at Gosan background site in the outflow from northeast Asia - Md. Mozammel Haque; Yan-lin Zhang; Dhananjay K. Deshmukh; Meehye Lee; Kimitaka Kawamura (Science of The Total Environment, 2024)

Seismic data, cross-section balancing, and hydrocarbon prospectivity of the western Sulaiman fold belt, northwest Pakistan - Saif-ur-Rehman K. Jadoon; Lin Ding; Ishtiaq A.K. Jadoon; Jabir Nazir; Fan Ping (Marine and Petroleum Geology, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Simultaneous generation of free radicals, Fe(IV) and Fe(V) by ferrate activation: A review - Feilong Dong; Chuyun Fu; Mingbao Feng; Da Wang; Shuang Song; Cong Li; Eric Lichtfouse; Jinzhe Li; Qiufeng Lin; Virender K. Sharma (Chemical Engineering Journal, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Treatment of Lateral Canthal Lines With RelabotulinumtoxinA, an Investigational Liquid Botulinum Toxin: Clinical Efficacy and Safety Results From the READY-2 Phase 3 Trial - Glynis Ablon; David Bank; Theda Kontis; Sherrif F Ibrahim; Melanie Palm; Sue Ellen Cox; Jason K Rivers; Lisa Grunebaum; Mitchel P Goldman; Shannon Humphrey; Xiaoming Lin; Schafiq Nabhani; et al. (Toxicon, 2024)

Insights on volatile metals in landfill gas as determined from advanced treatment media - Thomas J. Smallwood; Jordan K. Magnuson; Jake T. Thompson; Ashley M. Lin; Timothy G. Townsend (Journal of Hazardous Materials, 2024)

Effect of micro-fin tube geometry parameters on evaporator material savings - M.A. Kedzierski; L. Lin; K. Han (International Journal of Refrigeration, 2024)

Possibility of condensation of nitric acid for cloud condensation nucleus in the summer at Mt. Fuji - Kojiro Shimada; Yoshun Geka; Shungo Kato; Chak K. Chan; Yong Pyo Kim; Chang-Feng Ou-Yang; Neng-Huei Lin; Shiro Hatakeyama (Atmospheric Pollution Research, 2024)

Aquaculture in Zambia: The Current Status, Challenges, Opportunities and Adaptable Lessons Learnt from China - Lin Zhang; Sahya Maulu; Fenglei Hua; Majory K. H. Chama; Pao Xu (Fishes, 2023)
As a land-locked country in Southern Africa, Zambia is rich in natural resources suitable for fish production. However, aquaculture is still in its infancy with enormous potential as most of Zambia’s fish now comes from capture fisheries. The aim of this study was to review the recent progress, status, challenges, and opportunities in Zambia’s aquaculture industry while drawing some lessons from China’s aquaculture experience, focusing on policy instruments, external support, quality seeds, and the investment environment for possible adaptation. To achieve this, we reviewed the existing literature about aquaculture in Zambia. This paper starts by reviewing the overall fishery sector’s developments based on the analysis of relevant statistics over decades before narrowing down to the aquaculture sub-sector. The review shows that aquaculture production has continued to expand significantly and will soon play a leading role in food and nutrition security in Zambia. However, the industry still faces major challenges relating to investments, science and technology, fish seed and feed, and an underdeveloped value chain besides the increasing demand for fish products. Nevertheless, great potential still exists to further develop the aquaculture sub-sector and meet the ever-growing demand for fish products caused mainly by the rapid population increase.

Novel Selective Quantification of Zinpentraxin Alfa Biotherapeutic in the Presence of Endogenous Isomer in Plasma Samples of Idiopathic Pulmonary Fibrosis Patients Using Immunoaffinity LC–MS - Maoyin Li; Audrey Arjomandi; Xiaowei Sun; Erhu Lu; Tulika Tyagi; WeiYu Lin; Saloumeh K. Fischer; Surinder Kaur; Keyang Xu (The AAPS Journal, 2023)
Idiopathic pulmonary fibrosis (IPF) is a progressive fatal interstitial lung disease that affects three million patients worldwide and currently without an effective cure. Zinpentraxin alfa, a recombinant human pentraxin-2 (rhPTX-2) protein, has been evaluated as a potential drug candidate for the treatment of IPF. Clinical pharmacokinetic analysis of zinpentraxin alfa has been challenging historically due to interference from serum amyloid P component (SAP), an endogenous human pentraxin-2 protein. These molecules share an identical primary amino acid sequence and glycan composition; however, zinpentraxin alfa possesses α2,3-linked terminal sialic acid residues while SAP is an α2,6-linked isomer. By taking advantage of this only structural difference, we developed a novel assay strategy where α2,3-sialidase was used to selectively hydrolyze α2,3-linked sialic acid residues, resulting in desialylated zinpentraxin alfa versus unchanged sialylated SAP, following an immunoaffinity capture step. Subsequent tryptic digestion produced a unique surrogate asialo-glycopeptide from zinpentraxin alfa and allowed specific quantification of the biotherapeutic in human plasma. In addition, a common peptide shared by both molecules was selected as a surrogate to determine total hPTX-2 concentrations, i.e., sum of zinpentraxin alfa and SAP. The quantification methods for both zinpentraxin alfa and total hPTX-2 were validated and used in pharmacokinetic assessment in IPF patients. The preliminary results suggest that endogenous SAP levels remained largely constant in IPF patients throughout the treatment with zinpentraxin alfa. Our novel approach provides a general bioanalytical strategy to selectively quantify α2,3-sialylated glycoproteins in the presence of their corresponding α2,6-linked isomers. Graphical Abstract

Green synthesis of silver nanomaterials and evaluation of their antibacterial and antioxidant effectiveness in chicken meat - Fouad K. Alsammarraie; Mengshi Lin; Azlin Mustapha (Food Bioscience, 2023)

A simultaneous facility location and vehicle routing problem with recyclable express packaging consideration for sustainable city logistics - Yuhe Shi; Yun Lin; Songyi Wang; Haolin Wen; Ming K. Lim; Yan Li (Sustainable Cities and Society, 2023)

Generating high spatial resolution exposure estimates from sparse regulatory monitoring data - Yihui Ge; Zhenchun Yang; Yan Lin; Philip K. Hopke; Albert A. Presto; Meng Wang; David Q. Rich; Junfeng Zhang (Atmospheric Environment, 2023)

Tropospheric ozone is a catastrophe, and ethylenediurea (EDU) is a phytoprotectant, recent reports on climate change scenario: A review - Sunil K. Gupta; Yang Da; Yun-Bing Zhang; Vivek Pandey; Jiao-Lin Zhang (Atmospheric Pollution Research, 2023)

On the harmonic correction in the gravity field determination - Meng Yang; Xiaopeng Li; Miao Lin; Xiao-Le Deng; Wei Feng; Min Zhong; C. K. Shum; Daniel R. Roman (Journal of Geodesy, 2023)

Are associations between obesity and prostate cancer outcomes following radical prostatectomy the same in smokers and non-smokers? Results from the SEARCH Cohort - Ivy T. Liu; Lin Gu; Amanda M. De Hoedt; Matthew R. Cooperberg; Christopher L. Amling; Christopher J. Kane; Zachary Klaassen; Martha K. Terris; Lourdes Guerrios-Rivera; Adriana C. Vidal; William J. Aronson; Stephen J. Freedland; et al. (Cancer Causes & Control, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Field reconnaissance and observations from the February 6, 2023, Turkey earthquake sequence - Gulen Ozkula; Robert K. Dowell; Tugce Baser; Jui-Liang Lin; Ozgun A. Numanoglu; Okan Ilhan; C. Guney Olgun; Cheng-Wei Huang; Tunc Deniz Uludag (Natural Hazards, 2023)

Fixation of CO2 by soil fungi: contribution to organic carbon pool and destination of fixed carbon products - Fang Li; Zhong-Jun Jia; Lin Chen; Yan-Lai Han; Yuan-Feng Cai; Brajesh K. Singh; Jia-Bao Zhang (Biology and Fertility of Soils, 2023)

A concise chemoenzymatic total synthesis of neutral Globo-series glycosphingolipids Globo A and Globo B, and Forssman and para-Forssman antigens - Yu-Ching Chiang; Chun-Yen Wu; Pei-Yun Chiang; Avijit K. Adak; Chun-Cheng Lin (Glycoconjugate Journal, 2023)

Enzymatically hydrolyzed fluorescence-based chemical probe enables in situ mapping of chitinase activity in the rhizosphere - Elias K. Zegeye; Vivian S. Lin; Jamie R. Nuñez; Nick A. Sconzo; Samuel O. Purvine; Aaron T. Wright; James J. Moran (Soil Biology and Biochemistry, 2023)

Clinical Nutrition Dashboard for Effective Tracking of Nutrition Metrics - G. Singer; K. Lin; A. Chawla; A. Khan; J. Monclova (Journal of the Academy of Nutrition and Dietetics, 2023)

Mn-MOFs-derived Mn2O3 as an effective peroxymonosulfate activator for the degradation of organics in water - V. D. Thao; N. T. Dung; N. D. Duc; T. T. Trang; D. T. M. Thanh; N. T. Phuong; N. T. Thuy; K.-Y. A. Lin; N. N. Huy (International Journal of Environmental Science and Technology, 2023)

Emerging polycyclic aromatic hydrocarbon (PAH) and trace metal leachability from reclaimed asphalt pavement (RAP) - Ashley M. Lin; Alina S. Timshina; Jordan K. Magnuson; John A. Bowden; Timothy G. Townsend (Chemosphere, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

An updated review on chemical compositions, biological capabilities, and clinical benefits of cranberries - Naymul Karim; Ahmed K. Rashwan; Shiyu Liu; Jitbanjong Tangpong; Tao Lin; Wei Chen (Food Bioscience, 2023)

Exploring the Inner Lens: Examining Oncology Consultants’ Use of Competency and Assessment Frameworks in Clinical Teaching Settings - Cindy Lin; Timothy K. Nguyen; Michael Sanatani (Journal of Cancer Education, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Identification of Heterotopic Mineralization and Adjacent Pathology in the Equine Fetlock Region by Low-Field Magnetic Resonance Imaging, Cone-Beam and Fan-Beam Computed Tomography - Szu-Ting Lin; Vanessa G. Peter; Stefano Schiavo; Rachel Pokora; Hayley Patrick; Nick Bolas; Alastair K. Foote; David R. Sargan; Rachel C. Murray (Journal of Equine Veterinary Science, 2023)

Up in the air: Polyfluoroalkyl phosphate esters (PAPs) in airborne dust captured by air conditioning (AC) filters - Alina S. Timshina; William J. Sobczak; Emily K. Griffin; Ashley M. Lin; Timothy G. Townsend; John A. Bowden (Chemosphere, 2023)

Movement patterns and habitat use of adult giant trevally (Caranx ignobilis) in the South China Sea - Wei-Chuan Chiang; Shian-Jhong Lin; Ker-Yea Soong; Te-Yu Liao; Yu-Yun Chen; Yuan-Shing Ho; Chen-Te Tseng; Michael K. Musyl (Marine Biology, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Melatonin reduces pink rib discoloration in wounded lettuce midribs - Catherine E. Belisle; Steven A. Sargent; Germán V. Sandoya; Jeffrey K. Brecht; Ru Dai; Bryce Askey; Zhentian Lei; Makou Lin; Jeongim Kim (Postharvest Biology and Technology, 2023)

Probing air pollution in the Taichung metropolitan area, Taiwan.Part 1: Comprehensive model evaluation and the spatial-temporal evolution of a PM2.5 pollution event - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Wei-Nai Chen; Chian-Yi Liu; Chih-Chung Chang (Atmospheric Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

July 2020 heavy rainfall in Japan: effect of real-time river discharge on ocean circulation based on a coupled river-ocean model - Yu-Lin K. Chang; Sergey M. Varlamov; Xinyu Guo; Toru Miyama; Yasumasa Miyazawa (Ocean Dynamics, 2023)
In July 2020, a stationary atmospheric front over Japan caused persistent, nearly continuous rain for most of the month that resulted in new historical highest rainfall records in several areas and caused serious river floods, landslides, and debris-flow events. An existing hindcast and forecast ocean circulation model that includes climatological discharge information of major rivers failed to represent the extreme river discharge under heavy rainfall. New experiments were conducted using real-time river discharge information based on Today's Earth CaMa-Flood simulation that includes 368 rivers in Japan. The inclusion of real-time river discharge improved the salinity bias in the near-surface waters. The differences were significant compared to the observations in the heavy rain region (i.e., Ariake Bay and Tosa Bay), and insignificant at offshore stations. The ensemble experiments of real-time river discharge cases suggested the difference between the climatological and the real-time river discharge experiments was not random, but was robust. The freshening water changed the shelf circulation, and its far-reaching effect appeared hundreds of kilometers away from the shore. Passive particle tracking was conducted for examining the cross-shelf exchange. More particles released from Bungo Channel went offshore in near-surface water when the real-time river discharge was used compared to using the climatology discharge. Particles released in Tosa Bay, Seto Inland Sea, and Kii Channel showed the opposite tendency. The real-time river discharge not only changed the modeled coastal salinity distribution, but also the coastal and offshore currents. The role of the real-time river discharge on modeling normal flow periods or drought events, and its influence on a longer time scale model simulation remain to be explored.

Resource saving and carbon footprint reduction potential of urban symbiosis strategy in express packaging waste recycling network - Yuhe Shi; Yun Lin; Songyi Wang; Haolin Wen; Ming K. Lim; Ming-Lang Tseng (Waste Management, 2023)

An external exposome-wide association study of opioid use disorder diagnosed during pregnancy in Florida - Boya Lin; Yi Zheng; Dikea Roussos-Ross; Kelly K. Gurka; Matthew J. Gurka; Hui Hu (Science of The Total Environment, 2023)

Embedded information of aerosol type, hygroscopicity and scattering enhancement factor revealed by the relationship between PM2.5 and aerosol optical depth - Kuo-En Chang; Ta-Chih Hsiao; Si-Chee Tsay; Tang-Huang Lin; Stephen M. Griffith; Chian-Yi Liu; Charles C.-K. Chou (Science of The Total Environment, 2023)

Planetary cross-linked structure design of hybrid organosilica membrane by amine-driven polymerization for CO2 separation - Jing-Yi Li; Yu-Ting Lin; David K. Wang; Hui-Hsin Tseng; Ming-Yen Wey (Journal of Cleaner Production, 2023)

Corrosion and bacterial growth mitigation in the desalination plant by imidazolium based ionic liquid: Experimental, surface and molecular docking analysis - Ambrish Singh; K.R. Ansari; Neeta Raj Sharma; Shivani Singh; Rahul Singh; Anu Bansal; Ismat H. Ali; Muhammad Younas; Abdullah K. Alanazi; Yuanhua Lin (Journal of Environmental Chemical Engineering, 2023)

An overview of 2D metal sulfides and carbides as Na host materials for Na-ion batteries - Javed Rehman; Shiru Lin; Mehwish K. Butt; Xiaofeng Fan; Tamer Khattab; Khaled A. Elsayed; Mohamed F. Shibl (Chemical Engineering Journal, 2023)

Yam Seep at Four-Way Closure Ridge: a prominent active gas seep system at the accretionary wedge SW offshore Taiwan - Yiting Tseng; Miriam Römer; Saulwood Lin; Thomas Pape; Christian Berndt; Tzu-Ting Chen; Charles K. Paull; David W. Caress; Gerhard Bohrmann (International Journal of Earth Sciences, 2023)
Hydroacoustic surveys at the accretionary wedge southwest of Taiwan reveal a confined active hydrocarbon seepage area of ~ 49,000 m 2 in ~ 1350 m water depth on the northern crest of the Four-Way Closure Ridge, which we call Yam Seep. In this study, multibeam and side-scan sonar data acquired during surveys with an autonomous underwater vehicle during an expedition with R/V Ocean Researcher I in 2017 showed that the area is characterized by rough topography and high seafloor backscatter. Seafloor observations with a video sled and sediment sampling with gravity corers and the MeBo seafloor drill rig during an expedition with R/V SONNE in 2018 revealed that the area is almost entirely covered by intensely fractured methane-derived carbonates, which indicate that seepage has been ongoing for thousands of years. Hydroacoustic anomalies (‘flares’) in the water column indicated the presence of several gas bubble emission sites mostly at the center and eastern flank of the area in 2019. Drilling through massive carbonates in the northwestern part of Yam Seep induced free gas escape from a depth of ~ 5.1 m. This suggests the presence of gas hydrates in the subsurface as the seep area is located well within the gas hydrate stability zone. The inter-disciplinary investigations of the Yam Seep demonstrate that upward migration of light hydrocarbons and seafloor discharge has a considerable influence on the seabed properties.

Historical biomonitoring of pollution trends in the North Pacific using archived samples from the Continuous Plankton Recorder Survey - Kefeng Li; Jane C. Naviaux; Sai Sachin Lingampelly; Lin Wang; Jonathan M. Monk; Claire M. Taylor; Clare Ostle; Sonia Batten; Robert K. Naviaux (Science of The Total Environment, 2023)

Long-term exposure to particulate matter and COPD mortality: Insights from causal inference methods based on a large population cohort in southern China - Ying Wang; Zhicheng Du; Yuqin Zhang; Shirui Chen; Shao Lin; Philip K. Hopke; David Q. Rich; Kai Zhang; Xiaobo X. Romeiko; Xinlei Deng; Yanji Qu; Yu Liu; et al. (Science of The Total Environment, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

A systematic evidence map for the evaluation of noncancer health effects and exposures to polychlorinated biphenyl mixtures - Laura M. Carlson; Krista Christensen; Sharon K. Sagiv; Pradeep Rajan; Carolyn R. Klocke; Pamela J. Lein; Evan Coffman; Rachel M. Shaffer; Erin E. Yost; Xabier Arzuaga; Pam Factor-Litvak; Alexander Sergeev; et al. (Environmental Research, 2023)

Macroscale superlubricity and durability of in situ grown hydrogenated graphene coatings - Shuyu Fan; Shu Xiao; Songsheng Lin; Fenghua Su; Yifan Su; Paul K. Chu (Chemical Engineering Journal, 2023)

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Possible influence of typhoons, volcanic ash, and ocean productivity on early larval survival and Japanese eel annual cohort recruitment - Yu-Lin K. Chang; Michael J. Miller (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

The Development and Characterization of a Highly Sensitive Mature TGFβ3 Assay to Evaluate Anti-TGFβ3 Target Engagement - A. Francesca Setiadi; Gizette Sperinde; Melissa Cheu; Wei-Ching Liang; WeiYu Lin; Connie Mahood; Saloumeh K. Fischer (The AAPS Journal, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

Learning from arid and urban aquatic ecosystems to inform more sustainable and resilient futures - Lauren McPhillips; Marta Berbés-Blázquez; Rebecca Hale; Tamara K. Harms; Vanya Bisht; Liliana Caughman; Sandra M. Clinton; Elizabeth Cook; Xiaoli Dong; Jennifer Edmonds; Sarah Gergel; Rosa Gómez; et al. (Journal of Hydrology, 2023)

Valorization of nano-based lignocellulosic derivatives to procure commercially significant value-added products for biomedical applications - Vickram AS; Gopalakrishnan Kumar; Nibedita Dey; Rohini Karunakaran; Anbarasu K; Anil Kumar Patel; Thanigaivel S; Gangadhar Andaluri; Yuan-Chung Lin; Deena Santhana Raj; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

Spatial and seasonal variations in the carbon and lead isotopes of PM2.5 in air of residential buildings and their applications for source identification - Chien-Cheng Jung; Yang-Hsueh Chen; Charles C.-K. Chou; Yi-Tang Huang; Kuan-Ting Lin (Environmental Pollution, 2023)

Triggering of ST-elevation myocardial infarction by ultrafine particles in New York: Changes following Tier 3 vehicle introduction - Catherine S. Yount; Mark J. Utell; Philip K. Hopke; Sally W. Thurston; Shao Lin; Frederick S. Ling; Yunle Chen; David Chalupa; Xinlei Deng; David Q. Rich (Environmental Research, 2023)

Are African countries on track to achieve their NDCs pledges? Evidence from difference-in-differences technique - Hermas Abudu; Presley K. Wesseh; Boqiang Lin (Environmental Impact Assessment Review, 2023)

Life-course exposure to ambient fine particulate matter and hypertension in adulthood: a longitudinal cohort study - Cui Guo; Ly-yun Chang; Yacong Bo; Changqing Lin; Alexis K. H. Lau; Tony Tam; Xiang Qian Lao (Environmental Science and Pollution Research, 2023)

Cover Image - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)

Exogenous polyunsaturated fatty acids ( PUFAs ) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A ‐layer strain of Aeromonas salmonicida - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)
Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore the ability of non‐A‐layer and A‐layer A. salmonicida strains to incorporate polyunsaturated fatty acids (PUFAs) into their lipid profile and test the phenotypic effects thereof. Lipids were extracted from PUFA‐exposed cultures and analysed for lipid modification by thin‐layer chromatography and ultraperformance liquid chromatography‐mass spectrometry, showing A. salmonicida , regardless of A‐layer, capable of incorporating all seven of the PUFAs studied. Phenotypic effects were determined through the use of assays that tested for biofilm formation, membrane permeability and cyclic peptide susceptibility. Temperature‐dependent effects on biofilm formation were observed, and PUFA exposure showed significant ( p

Can Soluble Immune Checkpoint Molecules on Exosomes Mediate Inflammation? - Julie Joseph; Benjamin Rahmani; Yonesha Cole; Neha Puttagunta; Edward Lin; Zafar K. Khan; Pooja Jain (Journal of Neuroimmune Pharmacology, 2022)

A comprehensive review on water stable metal-organic frameworks for large-scale preparation and applications in water quality management based on surveys made since 2015 - R. Y. Li; Z. S. Wang; Z. Y. Yuan; Constance Van Horne; Viatcheslav Freger; M. Lin; R. K. Cai; J. P. Chen (Critical Reviews in Environmental Science and Technology, 2022)

Physical activity from menarche-to-first pregnancy and risk of breast cancer: the California teachers study - Dan Lin; Ying Liu; Deirdre K. Tobias; Kathleen Sturgeon (Cancer Causes & Control, 2022)

Battery recycling policies for boosting electric vehicle adoption: evidence from a choice experimental survey - Xingjun Huang; Yun Lin; Feng Liu; Ming K. Lim; Lixu Li (Clean Technologies and Environmental Policy, 2022)

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

The association of cerebrospinal fluid pressure with optic nerve head and macular vessel density - Xiangxiang Liu; Mohamed M. Khodeiry; Danting Lin; Yunxiao Sun; Qing Zhang; Jiawei Wang; Richard K. Lee; Ningli Wang (Science China Life Sciences, 2022)

Genotype-Environment-Management Interactions in Biomass Yield and Feedstock Composition of Photoperiod-Sensitive Energy Sorghum - August Schetter; Cheng-Hsien Lin; Colleen Zumpf; Chunhwa Jang; Leo Hoffmann; William Rooney; D. K. Lee (BioEnergy Research, 2022)

Risk Assessment of Navigation Safety for Ferries - Wen-Kai K. Hsu; Jun-Wen Chen; Nguyen Tan Huynh; Yan-You Lin (Journal of Marine Science and Engineering, 2022)
This study aims to discuss a risk assessment of navigation safety for ferries. In this research, the risk factors (RFs) for the navigation safety of ferries are first investigated from relevant literature and ferry operational features. A fuzzy AHP (Analytic Hierarchical Process) approach is then proposed to weight those RFs, after which a continuous risk-matrix model is then developed to determine the RFs’ risk levels. Finally, to validate the practical application of the proposed model, ferries traveling across the Taiwan Strait were empirically investigated. The results may provide practical information for ferry operators to improve their safety performances. Further, the proposed risk assessment approach may provide references for related research in the safety management of short-distance passenger ships.

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Metabolic properties, gene functions, and biosafety analysis reveal the action of three rhizospheric plant growth-promoting bacteria of Jujuncao (Pennisetum giganteum) - Richard Yankey; Ibrahim N. A. Omoor; Joseph K. Karanja; Lifang Wang; Regassa Terefe Urga; Chew Hui Fang; Lin Dongmei; Hui Lin; Jacob Eyalira Okal; Ibrahim Lawandi Datti; Aimable Nsanzinshuti; Christopher Rensing; et al. (Environmental Science and Pollution Research, 2022)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Microbiome Associated With Gambierdiscus balechii Cultures Under Different Toxicity Conditions - Zhen Wu; Wai Hin Lee; Zijian Liu; Senjie Lin; Paul K. S. Lam (Frontiers in Marine Science, 2022)
Dinoflagellates, including harmful algal bloom species, are known to co-exist with and rely upon bacteria but how the microbiome changes with the physiologies of the cognate dinoflagellates is poorly understood. Here, we used 16S rRNA gene meta-barcoding to characterize the bacterial community in the cultures of Gambierdiscus balechii , a ciguatoxin-producing benthic dinoflagellate, under different nitrogen (N)-nutrient conditions and at different ciguatoxin-producing growth. The high-throughput sequencing of a total of 12 libraries generated 926,438 reads which were classified into 16 phyla. We observed a shift of the G. balechii -associated microbiome from N-replete to low-N conditions and from the early (low toxin) to the late exponential (high toxin) growth stage. Common across these conditions were species from families Rhodobacteraceae and Flavobacteriaceae. Species abundant in the low-N condition mainly included Planctomyces , Ekhidna , and Lactobacillus. Dominant or highly abundant microbial taxa in the high toxin-producing stage (N-replete, late exponential stage) were Oceanococcus and Marinoscillum . Under this condition, one Rhizobiales bacterium, Oricola , also increased in relative abundance. Our study documents the high diversity and dynamics of the G. balechii -associated microbiome, and identifies condition-specific sub-communities: the core (constitutive) microbiome that stably co-exists with G. balechii , the bacterial lineages that are responsive to N-nutrient variations, and species whose abundances are correlated with toxin content of the dinoflagellate. These findings demonstrate that particular bacterial groups are responsive to N-nutrient or toxicity changes of G. balechii and thus will be useful for further investigations on the associated microbiome’s interactions with benthic dinoflagellates and functions in the course of benthic harmful algae blooms.

Multilevel monte carlo for cortical circuit models - Zhuo-Cheng Xiao; Kevin K. Lin (Journal of Computational Neuroscience, 2022)

REPIMPACT - a prospective longitudinal multisite study on the effects of repetitive head impacts in youth soccer - Inga K. Koerte; Roald Bahr; Peter Filipcik; Jolien Gooijers; Alexander Leemans; Alexander P. Lin; Yorghos Tripodis; Martha E. Shenton; Nir Sochen; Stephan P. Swinnen; Ofer Pasternak (Brain Imaging and Behavior, 2022)
Repetitive head impacts (RHI) are common in youth athletes participating in contact sports. RHI differ from concussions; they are considered hits to the head that usually do not result in acute symptoms and are therefore also referred to as “subconcussive” head impacts. RHI occur e.g., when heading the ball or during contact with another player. Evidence suggests that exposure to RHI may have cumulative effects on brain structure and function. However, little is known about brain alterations associated with RHI, or about the risk factors that may lead to clinical or behavioral sequelae. REPIMPACT is a prospective longitudinal study of competitive youth soccer players and non-contact sport controls aged 14 to 16 years. The study aims to characterize consequences of exposure to RHI with regard to behavior (i.e., cognition, and motor function), clinical sequelae (i.e., psychiatric and neurological symptoms), brain structure, function, diffusion and biochemistry, as well as blood- and saliva-derived measures of molecular processes associated with exposure to RHI (e.g., circulating microRNAs, neuroproteins and cytokines). Here we present the structure of the REPIMPACT Consortium which consists of six teams of clinicians and scientists in six countries. We further provide detailed information on the specific aims and the design of the REPIMPACT study. The manuscript also describes the progress made in the study thus far. Finally, we discuss important challenges and approaches taken to overcome these challenges.

Observations of Suspended Particulate Matter Concentrations and Particle Size Distributions within a Macrotidal Estuary (Port Curtis Estuary, Australia) - Ryan J. K. Dunn; Jordan Glen; Hsin-Hui Lin; Sasha Zigic (Journal of Marine Science and Engineering, 2021)
An understanding of suspended particulate matter (SPM) dynamics is of great importance to design awareness and management strategies of estuaries. Using a Laser In Situ Scattering and Transmissiometry (LISST) instrument, variations in suspended particle size volumetric concentrations (VC) and particle size distributions (PSD) were measured at six sites within Port Curtis estuary (Australia). The port is a macrotidal estuary with significant economic and environmental importance. Observed VC and SPM sizes demonstrated spatial and temporal trends strongly controlled by the variable energy conditions operating on the neap and spring cycle timescale, with a clear trend towards increasing concentrations and decreasing SPM sizes with increasing tidal ranges. Mid-estuary sites were characterized by the greatest depth-averaged VC under transitional and spring conditions. Estuary-wide mean spring tide total water profile concentrations revealed a near 300% increase in comparison to neap tide condition concentrations. In the upper-estuary sites the mean contribution of the combined 2.5–35 µm size classes to the total profile PSDs was greatest during all tidal conditions, whilst within the lower-estuary site the combined 35–130 µm size classes were greatest. Mean contributions of the largest size class (300–500 µm) dominated surface-waters throughout the estuary during the neap tide period, which when compared with the transitional and spring tide conditions, demonstrated changes of −82% to −48% and −82% to −40%, respectively. Overall, the results from this case study provides further evidence of the important influence of neap and spring tidal regimes on SPM dynamics within estuarine settings and the need to observe parameter dynamics on such timescales.

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Coarser taxonomic resolutions are informative in revealing fish community abundance trends for the world’s warmest coral reefs - Yu-Jia Lin; Ruben H. Roa-Ureta; Abdullajid Usama Basali; Joselito Francis Albaran Alcaria; Reynaldo Lindo; Mohammad A. Qurban; Perdana K. Prihartato; Ali Qasem; Lotfi Rabaoui (Coral Reefs, 2021)

Antigen production and development of an indirect ELISA based on the nucleocapsid protein to detect human SARS-CoV-2 seroconversion - Marcelo S. Conzentino; Karl Forchhammer; Emanuel M. Souza; Fábio O. Pedrosa; Meri B. Nogueira; Sônia M. Raboni; Fabiane G. M. Rego; Dalila L. Zanette; Mateus N. Aoki; Jeanine M. Nardin; Bruna Fornazari; Hugo M. P. Morales; et al. (Brazilian Journal of Microbiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A Rhizobium bacterium and its population dynamics under different culture conditions of its associated toxic dinoflagellate Gambierdiscus balechii - Zhen Wu; Xiaohong Yang; Senjie Lin; Wai Hin Lee; Paul K. S. Lam (Marine Life Science & Technology, 2021)

Diversity, Distribution, and Density of Marine Mammals Along the Saudi Waters of the Arabian Gulf: Update From a Multi-Method Approach - Lotfi Rabaoui; Ruben H. Roa-Ureta; Lamia Yacoubi; Yu-Jia Lin; Rommel Maneja; Thadickal V. Joydas; Premlal Panickan; Jinoy Gopalan; Ronald Loughland; Perdana K. Prihartato; Ali Qassem; Tyas I. Hikmawan; et al. (Frontiers in Marine Science, 2021)
Despite the important role of marine mammals in marine ecosystems and the imperative for their conservation, there is still a great lack of information on the diversity, distribution, and density of these animals in the Saudi waters of the Arabian Gulf. To fill this gap, an integrative data-collection approach including fishermen’s questionnaires, opportunistic sighting reports, and directed boat-based surveys, was undertaken between 2016 and 2020, leading to the first scientific report of marine mammal diversity, distribution, and density in the region. The results of the different approaches carried out during the study confirmed a high diversity of cetaceans on the west coast of the study area, with bottlenose dolphins ( Tursiops aduncus ), humpback dolphins ( Sousa plumbea ) and dugongs ( Dugong dugon ) as the most common species. While the two dolphin species were found to be widely distributed in both coastal and offshore waters, D. dugon appears to occur exclusively in coastal waters in the southern part of the study area, mainly in the Gulf of Salwah. The presence of both species of dolphins increased during the summer months and in the vicinity of the numerous oil and gas facilities in this region. The distribution of the observed dolphins was found mostly within a 10–20 km radius around each facility. Other cetacean species observed less frequently in the area include Bryde’s whale ( Balaenoptera edeni ), killer whale ( Orcinus orca ), common dolphin ( Delphinus delphis ) and finless porpoise ( Neophocaena phocaenoides ). Regarding the density of marine mammals in the region, boat-based surveys confirmed the results of fishermen’s questionnaires and reports of opportunistic sightings, with bottlenose and humpback dolphins being the most abundant species. These results provide a baseline for policies oriented to the conservation of mammals in the Saudi waters of the Arabian Gulf.

Dietary inflammatory index and risk of colorectal adenoma: effect measure modification by race, nonsteroidal anti-inflammatory drugs, cigarette smoking and body mass index? - Fangcheng Yuan; Lin Deng; Xiangqing Sun; Zhengyi Chen; Nitin Shivappa; Ashutosh K. Sheth; Gregory S. Cooper; James R. Hebert; Li Li (Cancer Causes & Control, 2021)

Soil Bacterial Characteristics Under Four Habitats with Different Vegetation Communities on the Qinghai-Tibetan Plateau - Rui Wang; Miao Wang; Jing Wang; Jiahe Yao; Xinwei Li; Yinghua Lin; Fang K. Du (Wetlands, 2021)

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Neuroplastin expression is essential for hearing and hair cell PMCA expression - Xiao Lin; Michael G. K. Brunk; Pingan Yuanxiang; Andrew W. Curran; Enqi Zhang; Franziska Stöber; Jürgen Goldschmidt; Eckart D. Gundelfinger; Maike Vollmer; Max F. K. Happel; Rodrigo Herrera-Molina; Dirk Montag (Brain Structure and Function, 2021)
Hearing deficits impact on the communication with the external world and severely compromise perception of the surrounding. Deafness can be caused by particular mutations in the neuroplastin ( Nptn ) gene, which encodes a transmembrane recognition molecule of the immunoglobulin (Ig) superfamily and plasma membrane Calcium ATPase (PMCA) accessory subunit. This study investigates whether the complete absence of neuroplastin or the loss of neuroplastin in the adult after normal development lead to hearing impairment in mice analyzed by behavioral, electrophysiological, and in vivo imaging measurements. Auditory brainstem recordings from adult neuroplastin-deficient mice ( Nptn −/− ) show that these mice are deaf. With age, hair cells and spiral ganglion cells degenerate in Nptn −/− mice. Adult Nptn −/− mice fail to behaviorally respond to white noise and show reduced baseline blood flow in the auditory cortex (AC) as revealed by single-photon emission computed tomography (SPECT). In adult Nptn −/− mice, tone-evoked cortical activity was not detectable within the primary auditory field (A1) of the AC, although we observed non-persistent tone-like evoked activities in electrophysiological recordings of some young Nptn −/− mice. Conditional ablation of neuroplastin in Nptn lox/loxEmx1Cre mice reveals that behavioral responses to simple tones or white noise do not require neuroplastin expression by central glutamatergic neurons. Loss of neuroplastin from hair cells in adult Nptn Δlox/loxPrCreERT mice after normal development is correlated with increased hearing thresholds and only high prepulse intensities result in effective prepulse inhibition (PPI) of the startle response. Furthermore, we show that neuroplastin is required for the expression of PMCA 2 in outer hair cells. This suggests that altered Ca 2+ homeostasis underlies the observed hearing impairments and leads to hair cell degeneration. Our results underline the importance of neuroplastin for the development and the maintenance of the auditory system.

Complete genome sequence of a previously undescribed monopartite begomovirus and betasatellite infecting Malvastrum coromandelianum in Cambodia - Yafei Tang; Zhenggang Li; Xiaoman She; Lin Yu; Guobing Lan; Lihua Lv; Judith K. Brown; Zifu He (Archives of Virology, 2021)

Human endothelial colony-forming cells provide trophic support for pluripotent stem cell-derived cardiomyocytes via distinctively high expression of neuregulin-1 - Xuechong Hong; Nicholas Oh; Kai Wang; Joseph Neumeyer; Chin Nien Lee; Ruei-Zeng Lin; Breanna Piekarski; Sitaram Emani; Arin K. Greene; Ingeborg Friehs; Pedro J. del Nido; Juan M. Melero-Martin (Angiogenesis, 2021)

Strengths and weaknesses in the long‐term sustainability of two sympatric seabreams ( Argyrops spinifer and Rhabdosargus haffara , S paridae) - Yu‐Jia Lin; Lotfi Rabaoui; Rommel H. Maneja; Abdu Rahiman Kambrath Pulikkoden; Panickan Premlal; Zahid Nazeer; Mohammad A. Qurban; Khaled Abdulkader; Perdana K. Prihartato; Ali M. Qasem; Nabil Fita; Ruben H. Roa‐Ureta (Journal of Fish Biology, 2021)
Argyrops spinifer and Rhabdosargus haffara are two sympatric seabream species making important contributions to fisheries landings in the western Arabian/Persian Gulf. We identified the strengths and weaknesses in the long‐term sustainability of A. spinifer and R. haffara stocks by integrating multiple sources of data, including fisheries catch and effort statistics, life history traits, scientific trawl surveys and historical length frequency distribution. Four strengths were identified in A. spinifer : wide distribution of juveniles, positive association to the network of de facto fishing exclusion areas created by hundreds of oil‐gas facilities, early maturation and the existence of large and old individuals. A. spinifer suffers from two potential weaknesses: slow growth rate and higher exploitation pressure on the small‐sized individuals. R. haffara , on the other hand, has a strength of having a short life span and a fast growth rate, characteristics that make it robust to unfavourable conditions. R. haffara suffers from two weaknesses: the lack of association to the oil and gas facilities, and the preference for nearshore shallow waters with stronger negative anthropogenic impacts. Identified strengths and weaknesses of these two sparids provided a preliminary assessment about their long‐term sustainability, as well as a roadmap about how to develop different management strategies to meet specific objectives.

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

Genetics of mouse behavioral and peripheral neural responses to sucrose - Cailu Lin; Masashi Inoue; Xia Li; Natalia P. Bosak; Yutaka Ishiwatari; Michael G. Tordoff; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

Genetic controls of Tas1r3-independent sucrose consumption in mice - Cailu Lin; Michael G. Tordoff; Xia Li; Natalia P. Bosak; Masashi Inoue; Yutaka Ishiwatari; Longhui Chen; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

A Millifluidic Perfusion Cassette for Studying the Pathogenesis of Enteric Infections Using Ex-Vivo Organoids - Reid L. Wilson; Sarah A. Hewes; Anubama Rajan; Shih-Ching Lin; Carolyn Bomidi; Takanori Iida; Mary K. Estes; Anthony W. Maresso; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2021)

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Object Detection and Tracking with UAV Data Using Deep Learning - A. Ancy Micheal; K. Vani; S. Sanjeevi; Chao-Hung Lin (Journal of the Indian Society of Remote Sensing, 2021)

ManoMap: an automated system for characterization of colonic propagating contractions recorded by high-resolution manometry - Niranchan Paskaranandavadivel; Anthony Y. Lin; Leo K. Cheng; Ian Bissett; Andrew Lowe; John Arkwright; Saeed Mollaee; Phil G. Dinning; Gregory O’Grady (Medical & Biological Engineering & Computing, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

Artificial selection in breeding extensively enriched a functional allelic variation in TaPHS1 for pre-harvest sprouting resistance in wheat - Shubing Liu; Danfeng Wang; Meng Lin; Sunish K. Sehgal; Lei Dong; Yuye Wu; Guihua Bai (Theoretical and Applied Genetics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Mitigating Climate Change for Sugarcane Improvement: Role of Silicon in Alleviating Abiotic Stresses - Krishan K. Verma; Pratiksha Singh; Xiu-Peng Song; Mukesh Kumar Malviya; Rajesh Kumar Singh; Gan-Lin Chen; Sushil Solomon; Yang-Rui Li (Sugar Tech, 2020)

Advanced psychometric testing on a clinical screening tool to evaluate insomnia: sleep condition indicator in patients with advanced cancer - Chung-Ying Lin; Andy S. K. Cheng; Vida Imani; Mohsen Saffari; Maurice M. Ohayon; Amir H. Pakpour (Sleep and Biological Rhythms, 2020)
Purpose To examine the psychometric properties of the Sleep Condition Indicator (SCI) using different psychometric approaches [including classical test theory, Rasch models, and receiver operating characteristics (ROC) curve] among patients with advanced cancer. Methods Through convenience sampling, patients with cancer at stage III or IV ( n = 859; 511 males; mean ± SD age = 67.4 ± 7.5 years) were recruited from several oncology units of university hospitals in Iran. All the participants completed the SCI, Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Hospital Anxiety and Depression Scale (HADS), General Health Questionnaire (GHQ), and Edmonton Symptom Assessment Scale (ESAS). In addition, 491 participants wore an actigraph device to capture objective sleep. Results Classical test theory [factor loadings from confirmatory factor analysis = 0.76–0.89; test–retest reliability = 0.80–0.93] and Rasch analysis [infit mean square (MnSq) = 0.63–1.31; outfit MnSq = 0.61–1.23] both support the construct validity of the SCI. The SCI had significant associations with ISI, PSQI, ESS, HADS, GHQ, and ESAS. In addition, the SCI has satisfactory area under ROC curve (0.92) when comparing a gold standard of insomnia diagnosis. Significant differences in the actigraphy measure were found between insomniacs and non-insomniacs based on the SCI score defined by ROC. Conclusion With the promising psychometric properties shown in the SCI, healthcare providers can use this simple assessment tool to target the patients with advanced cancer who are at risk of insomnia and subsequently provide personalized care efficiently.

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

Embryonic gene expression altered by maternal exposure to air pollution in rats - Zheng Li; Jianqing Ma; Youxi Lin; Jianxiong Shen; Zhanyong Wu; Matthew T. V. Chan; William K. K. Wu (Environmental Science and Pollution Research, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Correction to: Potato Cultivar Susceptibility to Pythium Leak as Influenced by Harvest and Early Storage Temperatures - Andrew K Hollingshead; Nora L. Olsen; Mike Thornton; Jeff S. Miller; Amy Hui-Mei Lin (American Journal of Potato Research, 2020)

Potato Cultivar Susceptibility to Pythium Leak as Influenced by Harvest and Early Storage Temperatures - Andrew K Hollingshead; Nora L. Olsen; Mike Thornton; Jeff S. Miller; Amy Hui-Mei Lin (American Journal of Potato Research, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

Fetal Transcatheter Trileaflet Heart Valve Hemodynamics: Implications of Scaling on Valve Mechanics and Turbulence - Hoda Hatoum; Shelley Gooden; Megan Heitkemper; Kevin M. Blum; Jason Zakko; Martin Bocks; Tai Yi; Yen-Lin Wu; Yadong Wang; Christopher K. Breuer; Lakshmi Prasad Dasi (Annals of Biomedical Engineering, 2020)

Gut microbial diversity across a contact zone for California voles: Implications for lineage divergence of hosts and mitonuclear mismatch in the assembly of the mammalian gut microbiome - Dana Lin; Eileen A. Lacey; Bryan H. Bach; Ke Bi; Christopher J. Conroy; Anton Suvorov; Rauri C. K. Bowie (Molecular Ecology, 2020)
Gut microbial diversity is thought to reflect the co‐evolution of microbes and their hosts as well as current host‐specific attributes such as genetic background and environmental setting. To explore interactions among these parameters, we characterized variation in gut microbiome composition of California voles ( Microtus californicus ) across a contact zone between two recently diverged lineages of this species. Because this contact zone contains individuals with mismatched mitochondrial‐nuclear genomes (cybrids), it provides an important opportunity to explore how different components of the genotype contribute to gut microbial diversity. Analyses of bacterial 16S rRNA sequences and joint species distribution modelling revealed that host genotypes and genetic differentiation among host populations together explained more than 50% of microbial community variation across our sampling transect. The ranked importance (most to least) of factors contributing to gut microbial diversity in our study populations were: genome‐wide population differentiation, local environmental conditions, and host genotypes. However, differences in microbial communities among vole populations (β‐diversity) did not follow patterns of lineage divergence (i.e., phylosymbiosis). Instead, among‐population variation was best explained by the spatial distribution of hosts, as expected if the environment is a primary source of gut microbial diversity (i.e., dispersal limitation hypothesis). Across the contact zone, several bacterial taxa differed in relative abundance between the two parental lineages as well as among individuals with mismatched mitochondrial and nuclear genomes. Thus, genetic divergence among host lineages and mitonuclear genomic mismatches may also contribute to microbial diversity by altering interactions between host genomes and gut microbiota (i.e., hologenome speciation hypothesis).

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Assessment of transmission risk in WSSV‐infected shrimp Litopenaeus vannamei upon cooking - Luis Fernando Aranguren Caro; Hung N. Mai; Linda Nunan; Joshua Lin; Brenda Noble; Arun K. Dhar (Journal of Fish Diseases, 2020)
White spot syndrome virus has been a threat to the global shrimp industry since it was discovered in Taiwan in 1992. Thus, shrimp‐producing countries have launched regulations to prevent import of WSSV‐infected commodity shrimp from endemic areas. Recently, cooked shrimp that is infected with WSSV tested positive by PCR. However, there is no study to determine the infectivity of WSSV in cooked shrimp that tested positive by PCR. In the present study, WSSV‐infected shrimp were cooked at boiling temperature for different times including 0, 1, 3, 5, 10 and 30 min. Upon exposure to boiling temperature, WSSV‐infected shrimp were fed to SPF shrimp ( Litopenaeus vannamei ). The result showed experimentally challenged shrimp from 0‐min treatment (positive control) indeed got infected with WSSV. However, experimentally challenged shrimp that were fed tissues boiled at 1, 3, 5, 10 and 30 min were not infected with WSSV. Mortality data showed that only the positive control (0‐min) treatment displayed high mortality, whereas no mortality was observed in any other treatment category. These findings suggest that cooking shrimp at boiling temperature for at least 1 min might prevent any potential spread of WSSV from endemic countries to other geographical areas where WSSV has not yet been reported.

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Potential changes to the biology and challenges to the management of invasive sea lamprey Petromyzon marinus in the Laurentian Great Lakes due to climate change - Robert J. Lennox; Gale A. Bravener; Hsien‐Yung Lin; Charles P. Madenjian; Andrew M. Muir; Christina K. Remucal; Kelly F. Robinson; Andrew M. Rous; Michael J. Siefkes; Michael P. Wilkie; Daniel P. Zielinski; Steven J. Cooke (Global Change Biology, 2020)
Control programs are implemented to mitigate the damage caused by invasive species worldwide. In the highly invaded Great Lakes, the climate is expected to become warmer with more extreme weather and variable precipitation, resulting in shorter iced‐over periods and variable tributary flows as well as changes to pH and river hydrology and hydrogeomorphology. We review how climate change influences physiology, behavior, and demography of a damaging invasive species, sea lamprey ( Petromyzon marinus ), in the Great Lakes, and the consequences for sea lamprey control efforts. Sea lamprey control relies on surveys to monitor abundance of larval sea lamprey in Great Lakes tributaries. The abundance of parasitic, juvenile sea lampreys in the lakes is calculated by surveying wounding rates on lake trout ( Salvelinus namaycush ), and trap surveys are used to enumerate adult spawning runs. Chemical control using lampricides (i.e., lamprey pesticides) to target larval sea lamprey and barriers to prevent adult lamprey from reaching spawning grounds are the most important tools used for sea lamprey population control. We describe how climate change could affect larval survival in rivers, growth and maturation in lakes, phenology and the spawning migration as adults return to rivers, and the overall abundance and distribution of sea lamprey in the Great Lakes. Our review suggests that Great Lakes sea lamprey may benefit from climate change with longer growing seasons, more rapid growth, and greater access to spawning habitat, but uncertainties remain about the future availability and suitability of larval habitats. Consideration of the biology of invasive species and adaptation of the timing, intensity, and frequency of control efforts is critical to the management of biological invasions in a changing world, such as sea lamprey in the Great Lakes.

The role of soil redox conditions in microbial phosphorus cycling in humid tropical forests - Avner Gross; Yang Lin; Peter K. Weber; Jennifer Pett‐Ridge; Whendee L. Silver (Ecology, 2020)
Humid tropical forests are among the most productive ecosystems globally, yet they often occur on soils with high phosphorus (P) sorption capacity, lowering P availability to biota. Short‐term anoxic events are thought to release sorbed P and enhance its acquisition by soil microbes. However, the actual effects of anoxic conditions on microbial P acquisition in humid tropical forest soils are surprisingly poorly studied. We used laboratory incubations of bulk soils, NanoSIMS analysis of single microbial cells, and landscape‐scale measurements in the Luquillo Experimental Forest (LEF), Puerto Rico to test the hypothesis that anoxic conditions increase microbial P acquisition in humid tropical forests. In laboratory and field experiments, we found that microbial P uptake generally decreased under anoxic conditions, leading to high microbial carbon (C) to P ratios in anoxic soils. The decreased P acquisition under anoxic conditions was correlated with lower microbial C use efficiency (CUE), an index of microbial energy transfer in ecosystems. Phosphorus amendments to anoxic soils led to increased microbial P uptake and higher CUE suggesting that microbes were less able to access and utilize P under natural low redox conditions. Under oxic conditions, microbial C:P ratios and CUE did not respond to changes in substrate stoichiometry. These results challenge the existing paradigm by showing that anoxic conditions can decrease microbial P uptake and ultimately constrain microbial CUE. Our findings indicate that soil redox conditions tightly couple soil P and C cycles and advance our understanding of controls on P cycling in humid tropical forest ecosystems.

Structural styles, hydrocarbon prospects, and potential of Miano and Kadanwari fields, Central Indus Basin, Pakistan - Saif-Ur-Rehman K. Jadoon; Ding Lin; Siddique Akhtar Ehsan; Ishtiaq A. K. Jadoon; Muhammad Idrees (Arabian Journal of Geosciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Study on arbor leaf and ring as a potential biological indicator for atmospheric polybrominated diphenyl ethers (PBDEs) distribution at e-wastes recycling sites - M. Gao; G. Wang; B. Lin; M. Tariq; K. Liu; W. Zhang (International Journal of Environmental Science and Technology, 2019)

Transgenic maize phosphoenolpyruvate carboxylase alters leaf–atmosphere CO2 and 13CO2 exchanges in Oryza sativa - Rita Giuliani; Shanta Karki; Sarah Covshoff; Hsiang-Chun Lin; Robert A. Coe; Nuria K. Koteyeva; Marc A. Evans; W. Paul Quick; Susanne von Caemmerer; Robert T. Furbank; Julian M. Hibberd; Gerald E. Edwards; et al. (Photosynthesis Research, 2019)

Simplified Tai Chi 6-Form Apparatus for Balance in Elderly People with Alzheimer’s Disease - Yin-Chou Lin; Wen-Chuin Hsu; Chien-Hung Chen; Chai-Wei Wang; Katie Pei-Hsuan Wu; Alice M. K. Wong (Journal of Medical and Biological Engineering, 2019)

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Wang Ma; Lin Song; Kenny Helsen; Yingchao Lin; Jiangping Cai; Qiang Yu; Zhengwen Wang; Melinda D. Smith; et al. (Plant and Soil, 2019)

Movement behaviour of released wild and farm-raised dolphinfish Coryphaena hippurus tracked by pop-up satellite archival tags - Shian-Jhong Lin; Michael K. Musyl; Sheng-Ping Wang; Nan-Jay Su; Wei-Chuan Chiang; Ching-Ping Lu; Kazuki Tone; Chang-Ying Wu; Akira Sasaki; Itsumi Nakamura; Kazuyoshi Komeyama; Ryo Kawabe (Fisheries Science, 2019)

The Eurasian Jet Streams as Conduits for East Asian Monsoon Variability - Jasti S. Chowdary; Kaiming Hu; G. Srinivas; Yu Kosaka; Lin Wang; K. Koteswara Rao (Current Climate Change Reports, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Noise exposure assessment and prevention around high-speed rail - K.-T. Tsai; M.-D. Lin; Y.-H. Lin (International Journal of Environmental Science and Technology, 2019)

Ocean Observations in Support of Studies and Forecasts of Tropical and Extratropical Cyclones - Ricardo Domingues; Akira Kuwano-Yoshida; Patricia Chardon-Maldonado; Robert E. Todd; George Halliwell; Hyun-Sook Kim; I.-I. Lin; Katsufumi Sato; Tomoko Narazaki; Lynn K. Shay; Travis Miles; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Normal increases in insulin-stimulated glucose uptake after ex vivo contraction in neuronal nitric oxide synthase mu (nNOSμ) knockout mice - Xinmei Zhang; Xuzhu Lin; Glenn K. McConell (Pflügers Archiv - European Journal of Physiology, 2019)

Uncertainty analysis of rainfall depth duration frequency curves using the bootstrap resampling technique - Jing Lin Ng; Samsuzana Abd Aziz; Yuk Feng Huang; Majid Mirzaei; Aimrun Wayayok; M K Rowshon (Journal of Earth System Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Limbic system structure volumes and associated neurocognitive functioning in former NFL players - Christian Lepage; Marc Muehlmann; Yorghos Tripodis; Jakob Hufschmidt; Julie Stamm; Katie Green; Pawel Wrobel; Vivian Schultz; Isabelle Weir; Michael L. Alosco; Christine M. Baugh; Nathan G. Fritts; et al. (Brain Imaging and Behavior, 2019)

Sensitivity of Numerical Simulations of a Mesoscale Convective System to Ice Hydrometeors in Bulk Microphysical Parameterization - Zhaoxia Pu; Chao Lin; Xiquan Dong; Steven K. Krueger (Pure and Applied Geophysics, 2019)

The urgent need for microbiology literacy in society - Kenneth Timmis; Ricardo Cavicchioli; José Luis Garcia; Balbina Nogales; Max Chavarría; Lisa Stein; Terry J. McGenity; Nicole Webster; Brajesh K. Singh; Jo Handelsman; Victor de Lorenzo; Carla Pruzzo; et al. (Environmental Microbiology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Modulation of the southern Indian Ocean dipole on the impact of El Niño–Southern Oscillation on Australian summer rainfall - Hainan Gong; Wen Zhou; Wen Chen; Lin Wang; Marco Y.‐T. Leung; Paxson K.‐Y. Cheung; Yue Zhang (International Journal of Climatology, 2019)
This study investigates the modulation of the southern Indian Ocean dipole (SIOD) upon the impacts of the El Niño–Southern Oscillation (ENSO) on Australian summer rainfall (ASR) on an inter‐annual timescale. First the SIOD is identified as an important factor influencing rainfall anomalies over northeastern Australia via a zonal vertical circulation spanning from the southern Indian Ocean (SIO) to northern Australia. When ENSO and the SIOD are out of phase, the El Niño‐induced anticyclonic and convection anomalies shift eastwards to Australia and induce pronounced negative rainfall anomalies in northern Australia. When ENSO and the SIOD are in phase, the anticyclonic and convection anomalies extend westwards and generate an anomalous zonal vertical circulation, inducing positive rainfall anomalies in northeastern Australia. These different shifts in the circulation and rainfall anomalies with the two types of ENSO–SIOD occurrences are essentially attributed to the opposite effects of the different phases of SIOD events. The out‐of‐phase and in‐phase combinations of ENSO and the SIOD also largely form the dominant patterns of ASR variation. The significant influence of the SIOD on ASR indicates that the phase of the SIOD should be taken into account in the prediction of austral summer climate over Australia.

What Promotes the Recovery of Salt Marsh Infauna After Oil Spills? - J. W. Fleeger; M. R. Riggio; I. A. Mendelssohn; Q. Lin; D. R. Deis; D. S. Johnson; K. R. Carman; S. A. Graham; S. Zengel; A. Hou (Estuaries and Coasts, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

First observations of Tridacna noae (Röding, 1798) (Bivalvia: Heterodonta: Cardiidae) in Christmas Island (Indian Ocean) - Mei Lin Neo; Jeffrey K. Y. Low (Marine Biodiversity, 2018)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

Behavioural responses of an Australian colubrid snake (Dendrelaphis punctulatus) to a novel toxic prey item (the Cane Toad Rhinella marina) - John Llewelyn; Neil C. Choyce; Benjamin L. Phillips; Jonathan K. Webb; David J. Pearson; Lin Schwarzkopf; Richard Shine (Biological Invasions, 2018)

Multiscale analyses on a massive immigration process of Sogatella furcifera (Horváth) in south-central China: influences of synoptic-scale meteorological conditions and topography - Qiu-Lin Wu; John K. Westbrook; Gao Hu; Ming-Hong Lu; Wan-Cai Liu; Gregory A. Sword; Bao-Ping Zhai (International Journal of Biometeorology, 2018)

An Attempt to Find a Suitable Biomass for Biochar-Based Polypropylene Biocomposites - Oisik Das; Nam Kyeun Kim; Mikael S. Hedenqvist; Richard J. T. Lin; Ajit K. Sarmah; Debes Bhattacharyya (Environmental Management, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Microarray-based expression analysis of phytohormone-related genes in rice seedlings during cyanide metabolism - Xiao-Zhang Yu; Yu-Juan Lin; Chun-Jiao Lu; Dharmendra K. Gupta (Environmental Science and Pollution Research, 2018)

Modulation of the MJO intensity over the equatorial western Pacific by two types of El Niño - Lu Wang; Tim Li; Lin Chen; Swadhin K. Behera; Tomoe Nasuno (Climate Dynamics, 2018)

Design of alternate solvent for recovery of residual palm oil: simultaneous optimization of process performance with environmental, health and safety aspects - Sarah Sue Lin Chang; Yuan Lin Kong; Wei Xuen Lim; Jecksin Ooi; Denny K. S. Ng; Nishanth G. Chemmangattuvalappil (Clean Technologies and Environmental Policy, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Identification of a mutation in CNNM4 by whole exome sequencing in an Amish family and functional link between CNNM4 and IQCB1 - Sisi Li; Quansheng Xi; Xiaoyu Zhang; Dong Yu; Lin Li; Zhenyang Jiang; Qiuyun Chen; Qing K. Wang; Elias I. Traboulsi (Molecular Genetics and Genomics, 2018)

Fine-Mode Aerosol Loading Over a Sub-Sahel Location and Its Relation with the West African Monsoon - Okechukwu K. Nwofor; Victor N. Dike; Zhaohui Lin; Rachel T. Pinker; Nnaemeka D. Onyeuwaoma (Aerosol Science and Engineering, 2018)

Short-chain fatty acids in control of energy metabolism - Jiamiao Hu; Shaoling Lin; Baodong Zheng; Peter C. K. Cheung (Critical Reviews in Food Science and Nutrition, 2018)

Differential expression of the PAL gene family in rice seedlings exposed to chromium by microarray analysis - Xiao-Zhang Yu; Wei-Jia Fan; Yu-Juan Lin; Fei-Fei Zhang; Dharmendra K. Gupta (Ecotoxicology, 2018)

On the ecological significance of pollen color: a case study in American trout lily ( Erythronium americanum ) - Emily J. Austen; Shang‐Yao Lin; Jessica R. K. Forrest (Ecology, 2018)
Evolutionary ecologists seek to explain the processes that maintain variation within populations. In plants, petal color variation can affect pollinator visitation, environmental tolerance, and herbivore deterrence. Variation in sexual organs may similarly affect plant performance. Within‐population variation in pollen color, as occurs in the eastern North American spring ephemeral Erythronium americanum , provides an excellent opportunity to investigate the maintenance of variation in this trait. Although the red/yellow pollen‐color polymorphism of E. americanum is widely recognized, it has been poorly documented. Our goals were thus (1) to determine the geographic distribution of the color morphs and (2) to test the effects of pollen color on components of pollen performance. Data provided by citizen scientists indicated that populations range from monomorphic red, to polymorphic, to monomorphic yellow, but there was no detectable geographic pattern in morph distribution, suggesting morph occurrence cannot be explained by a broad‐scale ecological cline. In field experiments, we found no effect of pollen color on the probability of predation by the pollen‐feeding beetle Asclera ruficollis , on the ability of pollen to tolerate UV ‐B radiation, or on siring success (as measured by the fruit set of hand‐pollinated flowers). Pollinators, however, exhibited site‐specific pollen‐color preferences, suggesting they may act as agents of selection on this trait, and, depending on the constancy of their preferences, could contribute to the maintenance of variation. Collectively, our results eliminate some hypothesized ecological effects of pollen color in E. americanum , and identify effects of pollen color on pollinator attraction as a promising direction for future investigation.

Temporal Profile and Severity Correlation of a Panel of Rat Spinal Cord Injury Protein Biomarkers - Zhihui Yang; Helen M. Bramlett; Ahmed Moghieb; Dongnan Yu; Ping Wang; Fan Lin; Carl Bauer; Tyler M. Selig; Emily Jaalouk; Amanda S. Weissman; Disa S. Rathore; Pammela Romo; et al. (Molecular Neurobiology, 2018)

Matrix Metalloproteinases MMP-1 and MMP-9 and Their Inhibitor TIMP-1 as Markers of Dilated Cardiomyopathy in Patients of Different Age - I. B. Antonov; K. L. Kozlov; E. M. Pal’tseva; O. V. Polyakova; N. S. Lin’kova (Bulletin of Experimental Biology and Medicine, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

Evaluation of toxicity of Deepwater Horizon slick oil on spat of the oyster Crassostrea virginica - Julien Vignier; Anne Rolton; Philippe Soudant; Fu-lin E. Chu; René Robert; Aswani K. Volety (Environmental Science and Pollution Research, 2018)

A possible explanation for the divergent projection of ENSO amplitude change under global warming - Lin Chen; Tim Li; Yongqiang Yu; Swadhin K. Behera (Climate Dynamics, 2017)

Approaches for Establishing Clinically Relevant Dissolution Specifications for Immediate Release Solid Oral Dosage Forms - Andre Hermans; Andreas M. Abend; Filippos Kesisoglou; Talia Flanagan; Michael J. Cohen; Dorys A. Diaz; Y. Mao; Limin Zhang; Gregory K. Webster; Yiqing Lin; David A. Hahn; Carrie A. Coutant; et al. (The AAPS Journal, 2017)

Stochastic modelling of seasonal and yearly rainfalls with low-frequency variability - Jing Lin Ng; Samsuzana Abd Aziz; Yuk Feng Huang; Aimrun Wayayok; M. K. Rowshon (Stochastic Environmental Research and Risk Assessment, 2017)

Expression of Signal Molecules in Culture of Human Endothelial Cells in Atherosclerosis and Restenosis - K. L. Kozlov; I. I. Bolotov; N. S. Lin’kova; A. O. Drobintseva (Bulletin of Experimental Biology and Medicine, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Controlled Release of Vanadium from a Composite Scaffold Stimulates Mesenchymal Stem Cell Osteochondrogenesis - S. D. Schussler; K. Uske; P. Marwah; F. W. Kemp; J. D. Bogden; S. S. Lin; Treena Livingston Arinzeh (The AAPS Journal, 2017)

Homologous gene targeting of a carotenoids biosynthetic gene in Rhodosporidium toruloides by Agrobacterium-mediated transformation - Wenyi Sun; Xiaobing Yang; Xueying Wang; Xinping Lin; Yanan Wang; Sufang Zhang; Yushi Luan; Zongbao K. Zhao (Biotechnology Letters, 2017)

The role of functional uniqueness and spatial aggregation in explaining rarity in trees - María Natalia Umaña; Xiangcheng Mi; Min Cao; Brian J. Enquist; Zhanqing Hao; Robert Howe; Yoshiko Iida; Daniel Johnson; Luxiang Lin; Xiaojuan Liu; Keping Ma; I‐Fang Sun; et al. (Global Ecology and Biogeography, 2017)
Aim Determining the drivers of species rarity is fundamental for understanding and conserving biodiversity. Rarity of a given species within its community may arise due to exclusion by other ecologically similar species. Conversely, rare species may occupy habitats that are rare in the landscape or they may be ill‐suited to all available habitats. The first mechanism would lead to common and rare species occupying similar ecological space defined by functional traits. The second mechanism would result in common and rare species occupying dissimilar ecological space and spatial aggregation of rare species, either because they are specialists in rare habitats or because rare species tend to be dispersal limited. Here, we quantified the contribution of locally rare species to community functional richness and the spatial aggregation of species across tree communities world‐wide to address these hypotheses. Location Asia and the Americas. Time period 2002 to 2012 (period that considers the censuses for the plots used). Major taxa studied Angiosperm and Gymnosperm trees. Methods We compiled a dataset of functional traits from all the species present in eight tree plots around the world to evaluate the contribution of locally rare species to tree community functional richness using multi‐ and univariate approaches. We also quantified the spatial aggregation of individuals within species at several spatial scales as it relates to abundance. Results Locally rare tree species in temperate and tropical forests tended to be functionally unique and are consistently spatially clustered. Furthermore, there is no evidence that this pattern is driven by pioneer species being locally rare. Main conclusions This evidence shows that locally rare tree species disproportionately contribute to community functional richness, and we can therefore reject the hypothesis that locally rare species are suppressed by ecologically similar, but numerically dominant, species. Rather, locally rare species are likely to be specialists on spatially rare habitats or they may be ill‐suited to the locally available environments.

A Test for Gene Flow among Sympatric and Allopatric Hawaiian Picture-Winged Drosophila - Lin Kang; Harold R. Garner; Donald K. Price; Pawel Michalak (Journal of Molecular Evolution, 2017)

CRISPR-Cas9 and CRISPR-Cpf1 mediated targeting of a stomatal developmental gene EPFL9 in rice - Xiaojia Yin; Akshaya K. Biswal; Jacqueline Dionora; Kristel M. Perdigon; Christian P. Balahadia; Shamik Mazumdar; Caspar Chater; Hsiang-Chun Lin; Robert A. Coe; Tobias Kretzschmar; Julie E. Gray; Paul W. Quick; et al. (Plant Cell Reports, 2017)

Sugarcane bagasse biochars impact respiration and greenhouse gas emissions from a latosol - Wangang Deng; Lukas Van Zwieten; Zhaomu Lin; Xingyuan Liu; Ajit K Sarmah; Hailong Wang (Journal of Soils and Sediments, 2017)

Dietary flavones counteract phorbol 12-myristate 13-acetate-induced SREBP-2 processing in hepatic cells - Yan Qin Tan; Tsz Yan Wong; Shu-mei Lin; Lai K. Leung (Molecular and Cellular Biochemistry, 2017)

Hydroregulation in a tropical dry-skinned ectotherm - Anna F. V. Pintor; Lin Schwarzkopf; Andrew K. Krockenberger (Oecologia, 2016)

Examining the Neural and Astroglial Protective Effects of Cellular Prion Protein Expression and Cell Death Protease Inhibition in Mouse Cerebrocortical Mixed Cultures - Kevin K. W. Wang; Zhihui Yang; Allen Chiu; Fan Lin; Richard Rubenstein (Molecular Neurobiology, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Changes in Sulforaphane and Selenocysteine Methyltransferase Transcript Levels in Broccoli Treated with Sodium Selenite - K. Huang; J. C. Lin; Q. Y. Wu; J. Y. Yan; M. Y. Liu; S. Zhang; W. J. Xiao (Plant Molecular Biology Reporter, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Distinctive precursory air–sea signals between regular and super El Niños - Lin Chen; Tim Li; Swadhin K. Behera; Takeshi Doi (Advances in Atmospheric Sciences, 2016)

Deep sequencing of banana bract mosaic virus from flowering ginger (Alpinia purpurata) and development of an immunocapture RT-LAMP detection assay - Jingxin Zhang; Wayne B. Borth; Birun Lin; Kishore K. Dey; Michael J. Melzer; Huifang Shen; Xiaoming Pu; Dayuan Sun; John S. Hu (Archives of Virology, 2016)

Reconstructing rice phenology curves with frequency-based analysis and multi-temporal NDVI in double-cropping area in Jiangsu, China - Hongshuo Wang; Hui Lin; Darla K. Munroe; Xiaodong Zhang; Pengfei Liu (Frontiers of Earth Science, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Diesel degradation in soil catalyzed by the addition of a bioagent - Y. Lin; J.-J. Lay; W. K. Shieh (International Journal of Environmental Science and Technology, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Evaluation of soil erosion risk for watershed management in Shenmu watershed, central Taiwan using USLE model parameters - B. S. Lin; K. Thomas; C. K. Chen; H. C. Ho (Paddy and Water Environment, 2016)

Parallel evolution of leaf morphology in gnetophytes - Yong Yang; Longbiao Lin; David K. Ferguson (Organisms Diversity & Evolution, 2015)

Three N-Glycosylation Sites of Human Acetylcholinesterase Shares Similar Glycan Composition - Miranda L. Xu; Wilson K. W. Luk; Kei M. Lau; Cathy W. C. Bi; Anthony W. M. Cheng; Amy G. W. Gong; Huangquan Lin; Karl W. K. Tsim (Journal of Molecular Neuroscience, 2015)

Fully automatic and nonparametric quantification of adipose tissue in fat–water separation MR imaging - Defeng Wang; Lin Shi; Winnie C. W. Chu; Miao Hu; Brian Tomlinson; Wen-Hua Huang; Tianfu Wang; Pheng Ann Heng; David K. W. Yeung; Anil T. Ahuja (Medical & Biological Engineering & Computing, 2015)

Roles of the Fibrous Superficial Zone in the Mechanical Behavior of TMJ Condylar Cartilage - Leonardo Ruggiero; Brandon K. Zimmerman; Miri Park; Lin Han; Liyun Wang; David L. Burris; X. Lucas Lu (Annals of Biomedical Engineering, 2015)

2,3,5-Trimethoxy-4-cresol, an anti-metastatic constituent from the solid-state cultured mycelium of Antrodia cinnamomea and its mechanism - Chin-Chung Lin; Ching-Chun Chen; Yueh-Hsiung Kuo; Jong-Tar Kuo; K. J. Senthil Kumar; Sheng-Yang Wang (Journal of Natural Medicines, 2015)

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor - X. J. Guo; Z. Y. Lu; P. Wang; H. Li; Z. Z. Huang; K. F. Lin; Y. D. Liu (Environmental Science and Pollution Research, 2015)

Prediction and validation of enzyme and transporter off-targets for metformin - Sook Wah Yee; Lawrence Lin; Matthew Merski; Michael J. Keiser; Aakash Gupta; Youcai Zhang; Huan-Chieh Chien; Brian K. Shoichet; Kathleen M. Giacomini (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Crustal thickening and extension induced by the Great Sumatra–Andaman earthquake of 26 December 2004: revealed by the seismic moment tensor element Mrr - J.-Y. Lin; C.-L. Lo; W.-N. Wu; J.-C. Sibuet; S.-K. Hsu; Y.-Y. Wen (Marine Geophysical Research, 2015)

Invasion biology of spotted wing Drosophila (Drosophila suzukii): a global perspective and future priorities - Mark K. Asplen; Gianfranco Anfora; Antonio Biondi; Deuk-Soo Choi; Dong Chu; Kent M. Daane; Patricia Gibert; Andrew P. Gutierrez; Kim A. Hoelmer; William D. Hutchison; Rufus Isaacs; Zhi-Lin Jiang; et al. (Journal of Pest Science, 2015)

Home paint exposures and risk of childhood acute lymphoblastic leukemia: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Catherine Metayer; Elizabeth Milne; Eleni Th. Petridou; Claire Infante-Rivard; Logan G. Spector; Jacqueline Clavel; John D. Dockerty; Luoping Zhang; Bruce K. Armstrong; Jérémie Rudant; Lin Fritschi; et al. (Cancer Causes & Control, 2015)

The interplay of sediment characteristics, depth, water temperature, and ocean currents shaping the biogeography of lancelets ( S ubphylum C ephalochordata) in the NW P acific waters - Hsiu‐Chin Lin; Jen‐Ping Chen; Benny K K Chan; Kwang‐Tsao Shao (Marine Ecology, 2015)
Lancelets (or amphioxus) are often found within the soft bottom of shallow tropical and temperate seas. The present study is the first to provide a fine‐scale biogeography of five species of lancelets ( A symmetron lucayanum , B ranchiostoma belcheri , B ranchiostoma japonicum , E pigonichthys cultellus , and E pigonichthys maldivensis ) in the NW Pacific and examine the effects of multiple environmental parameters. From multivariate analyses, the distribution and abundance patterns of lancelets were explained by a combination of factors comprising depth, temperature of the collecting month, mean temperature of the coldest month in the year, medium particle size and silt/clay ratio of the sediments. In addition, ocean currents also affect their distribution range. The major occurrence of A . lucayanum and E . maldivensis was associated with the warm K uroshio current, but E . maldivensis exhibited higher tolerance to low salinity and low temperature, and preferred substrata of slightly larger grain size, a lower ratio of suspended sediments, and deeper water. The closely related B . belcheri and B . japonicum exhibited fine‐scale habitat differentiation, and B . japonicum was abundant along the southern coast of C hina, where the salinity is lower in winter because of the C hina Coastal Current and the substratum is composed of very coarse sand with suspended sediments. Branchiostoma belcheri occurred in low abundance and was only recorded in N orthern T aiwan and the T aiwan Banks. Epigonichthys cultellus was found only at the T aiwan Banks, which had deep water, coarse sand, and a negligible amount of suspended sediments.

Characterization of a Novel Two-Component System in Burkholderia cenocepacia - Callie R. Merry; Michael Perkins; Lin Mu; Bridget K. Peterson; Rebecca W. Knackstedt; Christine L. Weingart (Current Microbiology, 2015)

Clustering of Clinical and Environmental Escherichia coli O104 Isolates Using the DiversiLab™ Repetitive Sequence-Based PCR System - N. M. Herbold; L. M. Clotilde; K. M. Anderson; J. Kase; G. L. Hartman; S. Himathongkham; A. Lin; C. R. Lauzon (Current Microbiology, 2015)

Clinical manifestations and prognostic factors of Morganella morganii bacteremia - T.-Y. Lin; M.-C. Chan; Y.-S. Yang; Y. Lee; K.-M. Yeh; J.-C. Lin; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Establishment of a novel, eco-friendly transgenic pig model using porcine pancreatic amylase promoter-driven fungal cellulase transgenes - Y. S. Lin; C. C. Yang; C. C. Hsu; J. T. Hsu; S. C. Wu; C. J. Lin; W. T. K. Cheng (Transgenic Research, 2015)

High seroprevalence of human herpesvirus type 8 in patients with hepatocellular carcinoma - C.-C. Su; K.-C. Tseng; M.-N. Lin; T.-C. Hsieh; T.-Y. Chu (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Removal of antineoplastic drugs cyclophosphamide, ifosfamide, and 5-fluorouracil and a vasodilator drug pentoxifylline from wastewaters by ozonation - Angela Yu-Chen Lin; Julia Han-Fang Hsueh; P. K. Andy Hong (Environmental Science and Pollution Research, 2015)

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

Numerical modeling of a strong dust event over the south China region in March 2010 - Kim-Chiu Chow; Lin Su; Jimmy C. H. Fung; Hui Ma; Alexis K. H. Lau (Meteorology and Atmospheric Physics, 2014)

Retention and release of diethyl phthalate in biochar-amended vegetable garden soils - Xiaokai Zhang; Lizhi He; Ajit K. Sarmah; Kunde Lin; Yingkun Liu; Jianwu Li; Hailong Wang (Journal of Soils and Sediments, 2014)

Molecular Aspects of Anti-Atherosclerotic Effects of Short Peptides - V. Kh. Khavinson; N. S. Lin’kova; E. V. Evlashkina; A. O. Durnova; K. L. Kozlov; O. E. Gutop (Bulletin of Experimental Biology and Medicine, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

A middle Cambrian shallow water trilobite fauna from the Comstock Formation, near Queenstown, western Tasmania - J. b. Jago; C. j. Bentley; Lin Tian-rui; K. d. Corbett (Australian Journal of Earth Sciences, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of pulmonary tuberculosis among patients with appendectomy in Taiwan - S.-W. Lai; C.-L. Lin; K.-F. Liao; S.-M. Tsai (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Erratum to: Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Development of a selective and differential medium for capsulated L actococcus garvieae - C‐I Chang; C‐F Lee; J‐M Tsai; C‐C Wu; L‐H Chen; S‐C Chen; K‐J Lin (Journal of Fish Diseases, 2014)
A selective and differential medium termed ‘ LG agar’ was developed for the isolation and presumptive identification of L actococcus garvieae that results in black colonies with red halos. In this study, all 14 strains of L . garvieae and only 9 of the 148 strains representing 38 other species were able to grow on the LG agar. The nine viable strains on LG agar plates (including E nterococcus faecalis , E nterococcus faecium , L actococcus lactis , V ibrio fluvialis , V ibrio furnissii , V ibrio mimicus and V ibrio salmonicida ) were further differentiated from L . garvieae by various colours or colony features. Colonies isolated from the mixing culture and the infected giant sea perch using LG agar plates were all positively identified as L . garvieae by conventional tests and 16 S r DNA sequencing. Furthermore, LG agar discriminated capsulated strains of L . garvieae , which were believed to be correlated with pathogens of fish and shellfish, from non‐capsulated ones by colony appearances. The specificity and differentiating ability of LG agar suggest that this medium displays considerable potential for primary isolation and presumptive identification of L . garvieae from pathological and environmental samples.

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Modulation of angiogenesis by thyroid hormone and hormone analogues: implications for cancer management - Shaker A. Mousa; Hung-Yun Lin; Heng Yuan Tang; Aleck Hercbergs; Mary K. Luidens; Paul J. Davis (Angiogenesis, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Imaging the Cytosolic Drug Delivery Mechanism of HDL-Like Nanoparticles - Qiaoya Lin; Juan Chen; Kenneth K. Ng; Weiguo Cao; Zhihong Zhang; Gang Zheng (Pharmaceutical Research, 2014)

Differential proteomic analysis of polyubiquitin-related proteins in chemical hybridization agent-induced wheat (Triticum aestivum L.) male sterility - Hongzhan Liu; Gaisheng Zhang; Wanwan Zhu; William K. K. Wu; Qingsong Ba; Lin Zhang; Longyu Zhang; Na Niu; Shoucai Ma; Junwei Wang (Acta Physiologiae Plantarum, 2014)

Pressure-assisted cyclic washing of heavy-metal-contaminated sediments - C. E. Lin; P. K. A. Hong; H. Y. Chiu; R. Y. Surampalli; C. T. Lin; C. M. Kao (International Journal of Environmental Science and Technology, 2014)

An ecological function and services approach to total maximum daily load (TMDL) prioritization - Robert K. Hall; David Guiliano; Sherman Swanson; Michael J. Philbin; John Lin; Joan L. Aron; Robin J. Schafer; Daniel T. Heggem (Environmental Monitoring and Assessment, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Childhood and parental diagnostic radiological procedures and risk of childhood brain tumors - Elizabeth Milne; Kathryn R. Greenop; Lin Fritschi; John Attia; Helen D. Bailey; Rodney J. Scott; Lesley J. Ashton; Elizabeth Smibert; Bruce K. Armstrong (Cancer Causes & Control, 2014)

Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Seismic performance and global ductility of RC frames rehabilitated with retrofitted joints by CFRP laminates - M. Fakharifar; M. K. Sharbatdar; Z. Lin; A. Dalvand; A. Sivandi-Pour; G. Chen (Earthquake Engineering and Engineering Vibration, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evacuees’ information sources and reentry decision making in the aftermath of Hurricane Ike - Chih-Chun Lin; Laura K. Siebeneck; Michael K. Lindell; Carla S. Prater; Hao-Che Wu; Shih-Kai Huang (Natural Hazards, 2014)

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

Human white adipose tissue vasculature contains endothelial colony-forming cells with robust in vivo vasculogenic potential - Ruei-Zeng Lin; Rafael Moreno-Luna; Rocio Muñoz-Hernandez; Dan Li; Shou-Ching S. Jaminet; Arin K. Greene; Juan M. Melero-Martin (Angiogenesis, 2013)

Pushover analysis of reinforced concrete frames considering shear failure at beam-column joints - Y. C. Sung; T. K. Lin; C. C. Hsiao; M. C. Lai (Earthquake Engineering and Engineering Vibration, 2013)

Prediction of the In Vivo Force–Velocity Relationship of Slow Human Skeletal Muscle from Measurements in Myofibers - Sampath K. Gollapudi; David C. Lin (Annals of Biomedical Engineering, 2013)

Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2013)

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

FOXO1-mediated upregulation of pyruvate dehydrogenase kinase-4 (PDK4) decreases glucose oxidation and impairs right ventricular function in pulmonary hypertension: therapeutic benefits of dichloroacetate - Lin Piao; Vaninder K. Sidhu; Yong-Hu Fang; John J. Ryan; Kishan S. Parikh; Zhigang Hong; Peter T. Toth; Erik Morrow; Shelby Kutty; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Fabrication and Mechanical Evaluation of Anatomically-Inspired Quasilaminate Hydrogel Structures with Layer-Specific Formulations - Hubert Tseng; Maude L. Cuchiara; Christopher A. Durst; Michael P. Cuchiara; Chris J. Lin; Jennifer L. West; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Relationships Between Nitrogen Transformation Rates and Gene Abundance in a Riparian Buffer Soil - Lin Wu; Deanna L. Osmond; Alexandria K. Graves; Michael R. Burchell; Owen W. Duckworth (Environmental Management, 2012)

Comparison of point and array-computed rotations for the TAIGER explosions of 4 March 2008 - Lauren M. Kendall; Charles A. Langston; W. H. K. Lee; C. J. Lin; C. C. Liu (Journal of Seismology, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Comparing the benefits of screening for breast cancer and lung cancer using a novel natural history model - Ray S. Lin; Sylvia K. Plevritis (Cancer Causes & Control, 2012)

Comparative analysis of phase I and II enzyme activities in 5 hepatic cell lines identifies Huh-7 and HCC-T cells with the highest potential to study drug metabolism - Jie Lin; Lilianna Schyschka; Ruben Mühl-Benninghaus; Jan Neumann; Liping Hao; Natascha Nussler; Steven Dooley; Liegang Liu; Ulrich Stöckle; Andreas K. Nussler; Sabrina Ehnert (Archives of Toxicology, 2012)

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

Parental occupational exposure to exhausts, solvents, glues and paints, and risk of childhood leukemia - Alison Reid; Deborah C. Glass; Helen D. Bailey; Elizabeth Milne; Bruce K. Armstrong; Frank Alvaro; Lin Fritschi (Cancer Causes & Control, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Object and spatial imagery dimensions in visuo-haptic representations - Simon Lacey; Jonathan B. Lin; K. Sathian (Experimental Brain Research, 2011)

Assessment of nitrogen contamination of groundwater in paddy and upland fields - Y. H. Kao; C.-W. Liu; C. S. Jang; S. W. Zanh; K. H. Lin (Paddy and Water Environment, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Invasion of the African sharp-tooth catfish Clarias gariepinus (Burchell, 1822) in South China - K. V. Radhakrishnan; Zhao Jun Lan; Jun Zhao; Ning Qing; Xio Lin Huang (Biological Invasions, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

A novel statistical method for classifying habitat generalists and specialists - Robin L. Chazdon; Anne Chao; Robert K. Colwell; Shang-Yi Lin; Natalia Norden; Susan G. Letcher; David B. Clark; Bryan Finegan; J. Pablo Arroyo (Ecology, 2011)
We develop a novel statistical approach for classifying generalists and specialists in two distinct habitats. Using a multinomial model based on estimated species relative abundance in two habitats, our method minimizes bias due to differences in sampling intensities between two habitat types as well as bias due to insufficient sampling within each habitat. The method permits a robust statistical classification of habitat specialists and generalists, without excluding rare species a priori. Based on a user‐defined specialization threshold, the model classifies species into one of four groups: (1) generalist; (2) habitat A specialist; (3) habitat B specialist; and (4) too rare to classify with confidence. We illustrate our multinomial classification method using two contrasting data sets: (1) bird abundance in woodland and heath habitats in southeastern Australia and (2) tree abundance in second‐growth (SG) and old‐growth (OG) rain forests in the Caribbean lowlands of northeastern Costa Rica. We evaluate the multinomial model in detail for the tree data set. Our results for birds were highly concordant with a previous nonstatistical classification, but our method classified a higher fraction (57.7%) of bird species with statistical confidence. Based on a conservative specialization threshold and adjustment for multiple comparisons, 64.4% of tree species in the full sample were too rare to classify with confidence. Among the species classified, OG specialists constituted the largest class (40.6%), followed by generalist tree species (36.7%) and SG specialists (22.7%). The multinomial model was more sensitive than indicator value analysis or abundance‐based phi coefficient indices in detecting habitat specialists and also detects generalists statistically. Classification of specialists and generalists based on rarefied subsamples was highly consistent with classification based on the full sample, even for sampling percentages as low as 20%. Major advantages of the new method are (1) its ability to distinguish habitat generalists (species with no significant habitat affinity) from species that are simply too rare to classify and (2) applicability to a single representative sample or a single pooled set of representative samples from each of two habitat types. The method as currently developed can be applied to no more than two habitats at a time.

Determining the subjective and physiological effects of BZP combined with TFMPP in human males - Joanne C. Lin; Reem K. Jan; HeeSeung Lee; Maree-Ann Jensen; Rob R. Kydd; Bruce R. Russell (Psychopharmacology, 2011)

Differential Proteomic Analysis of Temperature-Induced Autolysis in Mycelium of Pleurotus tuber-regium - Bifang Huang; Wenxiong Lin; Peter C. K. Cheung; Jinzhong Wu (Current Microbiology, 2011)

Resistance to a DNA and a RNA virus in transgenic plants by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Wen-Shi Tsai; Sylvia K. Green; Fuh-Jyh Jan (Transgenic Research, 2011)

ASIP genetic variants and the number of non-melanoma skin cancers - Wen Lin; Abrar A. Qureshi; Peter Kraft; Hongmei Nan; Qun Guo; Frank B. Hu; Majken K. Jensen; Jiali Han (Cancer Causes & Control, 2011)

Mobilization and transport of coarse woody debris to the oceans triggered by an extreme tropical storm - A. J. West; C.-W. Lin; T.-C. Lin; R. G. Hilton; S.-H. Liu; C.-T. Chang; K.-C. Lin; A. Galy; R. B. Sparkes; N. Hovius (Limnology and Oceanography, 2011)
A significant consequence of Typhoon Morakot in August 2009 was the production of vast volumes of driftwood in Pacific Asia. We have quantified the flux of this coarse woody debris (CWD) to the oceans from typhoon‐triggered landslides in Taiwan, where Morakot made landfall, by combining remote sensing (using FORMOSAT‐2 imagery and aerial photography), analysis of forest biomass, and field observations. A total of 3.8–8.4 Tg CWD was transported to the oceans, carrying 1.8–4.0 Tg of organic carbon. In addition to the local effects on the marine and coastal environment from such a highly concentrated flux of carbon and nutrients, storm‐driven mobilization of CWD may represent a significant, if infrequent, transfer of terrestrial biomass to the oceans. If the frequency of relatively rare, extreme storms such as Morakot increases in a changing climate, this transport mechanism may play an important role in feedbacks between global climate, storm intensity, and carbon cycling.

Global patterns in the biogeography of bacterial taxa - Diana R. Nemergut; Elizabeth K. Costello; Micah Hamady; Catherine Lozupone; Lin Jiang; Steven K. Schmidt; Noah Fierer; Alan R. Townsend; Cory C. Cleveland; Lee Stanish; Rob Knight (Environmental Microbiology, 2011)
Summary Bacteria control major nutrient cycles and directly influence plant, animal and human health. However, we know relatively little about the forces shaping their large‐scale ecological ranges. Here, we reveal patterns in the distribution of individual bacterial taxa at multiple levels of phylogenetic resolution within and between Earth's major habitat types. Our analyses suggest that while macro‐scale habitats structure bacterial distribution to some degree, abundant bacteria (i.e. detectable using 16S rRNA gene sequencing methods) are confined to single assemblages. Additionally, we show that the most cosmopolitan taxa are also the most abundant in individual assemblages. These results add to the growing body of data that support that the diversity of the overall bacterial metagenome is tremendous. The mechanisms governing microbial distribution remain poorly understood, but our analyses provide a framework with which to test the importance of macro‐ecological environmental gradients, relative abundance, neutral processes and the ecological strategies of individual taxa in structuring microbial communities.

Investigation of the association between all-trans-retinol dehydrogenase (RDH8) polymorphisms and high myopia in Chinese - Yan-shu Yu; Lin-ling Wang; Ye Shen; Maurice K. H. Yap; Shea-ping Yip; Wei Han (Journal of Zhejiang University-SCIENCE B, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Functional evaluation of therapeutic response for a mouse model of medulloblastoma - Aislynn K. Samano; Sachiko Ohshima-Hosoyama; Thomas G. Whitney; Suresh I. Prajapati; Aoife Kilcoyne; Eri Taniguchi; William W. Morgan; Laura D. Nelon; Ai-Ling Lin; Osamu Togao; Inkyung Jung; Brian P. Rubin; et al. (Transgenic Research, 2010)

Determining the subjective effects of TFMPP in human males - Reem K. Jan; Joanne C. Lin; HeeSeung Lee; Janie L. Sheridan; Rob R. Kydd; Ian J. Kirk; Bruce R. Russell (Psychopharmacology, 2010)

Simultaneous declines in radon and methane precursory to 2008 M W 5.0 Antung earthquake: corroboration of in-situ volatilization - T. Kuo; W. Cheng; C. Lin; K. Fan; G. Chang; T. Yang (Natural Hazards, 2010)

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Clinical and microbiological characteristics of community-acquired thoracic empyema or complicated parapneumonic effusion caused by Klebsiella pneumoniae in Taiwan - Y.-T. Lin; T.-L. Chen; L. K. Siu; S.-F. Hsu; C.-P. Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

WRN mutations in Werner syndrome patients: genomic rearrangements, unusual intronic mutations and ethnic-specific alterations - Katrin Friedrich; Lin Lee; Dru F. Leistritz; Gudrun Nürnberg; Bidisha Saha; Fuki M. Hisama; Daniel K. Eyman; Davor Lessel; Peter Nürnberg; Chumei Li; María J. Garcia-F-Villalta; Carolien M. Kets; et al. (Human Genetics, 2010)

Optimization of product line design for environmentally conscious technologies in notebook industry - K. H. Lin; L. H. Shih; S. C. Lee (International Journal of Environmental Science and Technology, 2010)

The second prolactin receptor in Nile tilapia (Oreochromis niloticus): molecular characterization, tissue distribution and gene expression - Yong Zhang; Zijie Long; Yangyuan Li; Shibai Yi; Yu Shi; Xilan Ma; Weiren Huang; Danqi Lu; Pei Zhu; Xiaochun Liu; Zining Meng; Xigui Huang; et al. (Fish Physiology and Biochemistry, 2010)

Estimation of aseismic crustal-strain using radon precursors of the 2003 M 6.8, 2006 M 6.1, and 2008 M 5.0 earthquakes in eastern Taiwan - T. Kuo; C. Lin; G. Chang; K. Fan; W. Cheng; C. Lewis (Natural Hazards, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Assessing the prospects of genome-wide association studies performed in inbred mice - Wan-Lin Su; Solveig K. Sieberts; Robert R. Kleinhanz; Karine Lux; Joshua Millstein; Cliona Molony; Eric E. Schadt (Mammalian Genome, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Velocity structure and gas hydrate saturation estimation on active margin off SW Taiwan inferred from seismic tomography - Win-Bin Cheng; S. S. Lin; T. K. Wang; C. S. Lee; C. S. Liu (Marine Geophysical Research, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Impact of GPS radio occultation data assimilation on regional weather predictions - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Chuen-Tsyr Terng; Fang-Ching Chien; Pay-Liam Lin; Mien-Tze Kueh; Shu-Hua Chen; Ming-Jen Yang; Chieh-Ju Wang; Anisetty S. K. A. V. Prasad Rao (GPS Solutions, 2010)

Model analyses of visual biofeedback training for EEG-based brain-computer interface - Chih-Wei Chen; Ming-Shaung Ju; Yun-Nien Sun; Chou-Ching K. Lin (Journal of Computational Neuroscience, 2009)

Modifier gene study of meconium ileus in cystic fibrosis: statistical considerations and gene mapping results - Ruslan Dorfman; Weili Li; Lei Sun; Fan Lin; Yongqian Wang; Andrew Sandford; Peter D. Paré; Karen McKay; Hana Kayserova; Tereza Piskackova; Milan Macek; Kamila Czerska; et al. (Human Genetics, 2009)

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Molecular characterization of two potato virus S isolates from late-blight-resistant genotypes of potato (Solanum tuberosum) - Y. H. Lin; K. L. Druffel; J. Whitworth; M. J. Pavek; Hanu R. Pappu (Archives of Virology, 2009)

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Spike-time reliability of layered neural oscillator networks - Kevin K. Lin; Eric Shea-Brown; Lai-Sang Young (Journal of Computational Neuroscience, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Identification of soil heavy metal sources from anthropogenic activities and pollution assessment of Fuyang County, China - X. Y. Zhang; F. F. Lin; Mike T. F. Wong; X. L. Feng; K. Wang (Environmental Monitoring and Assessment, 2009)

The Impact of Iodine Excess on Thyroid Hormone Biosynthesis and Metabolism in Rats - K. Wang; Y. N. Sun; J. Y. Liu; L. Zhang; Y. Ye; L. X. Lin; Y. Q. Yan; Z. P. Chen (Biological Trace Element Research, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

A genomic island of the sulfate‐reducing bacterium Desulfovibrio vulgaris Hildenborough promotes survival under stress conditions while decreasing the efficiency of anaerobic growth - Shawna Johnston; Shiping Lin; Phoebe Lee; Sean M. Caffrey; Janine Wildschut; Johanna K. Voordouw; Sofia M. Da Silva; Ines A. C. Pereira; Gerrit Voordouw (Environmental Microbiology, 2009)
Summary A 47 kb genomic island (GEI) bracketed by 50 bp direct repeats, containing 52 annotated genes, was found to delete spontaneously from the genome of Desulfovibrio vulgaris Hildenborough. The island contains genes for site‐specific recombinases and transposases, rubredoxin:oxygen oxidoreductase‐1 (Roo1) and hybrid cluster protein‐1 (Hcp1), which promote survival in air and nitrite stress. The numbering distinguishes these from the Roo2 and Hcp2 homologues for which the genes are located elsewhere in the genome. Cells with and without the island (GEI + and GEI ‐ cells respectively) were obtained by colony purification. GEI ‐ cells arise in anaerobic cultures of colony‐purified GEI + cells, indicating that the site‐specific recombinases encoded by the island actively delete this region. GEI + cells survive better in microaerophilic conditions due to the presence of Roo1, whereas the Hcps appear to prevent inhibition by sulfur and polysulfide, which are formed by chemical reaction of sulfide and nitrite. Hence, the island confers resistance to oxygen and nitrite stress. However, GEI ‐ cells have a higher growth rate in anaerobic media. Microarrays and enzyme activity stains indicated that the GEI ‐ cells have increased expression of genes, which promote anaerobic energy conservation, explaining the higher growth rate. Hence, while lowering the efficiency of anaerobic metabolism, the GEI increases the fitness of D. vulgaris under stress conditions, a feature reminiscent of pathogenicity islands which allow more effective colonization of environments provided by the targeted hosts.

Sufficient sampling for asymptotic minimum species richness estimators - Anne Chao; Robert K. Colwell; Chih-Wei Lin; Nicholas J. Gotelli (Ecology, 2009)
Biodiversity sampling is labor intensive, and a substantial fraction of a biota is often represented by species of very low abundance, which typically remain undetected by biodiversity surveys. Statistical methods are widely used to estimate the asymptotic number of species present, including species not yet detected. Additional sampling is required to detect and identify these species, but richness estimators do not indicate how much sampling effort (additional individuals or samples) would be necessary to reach the asymptote of the species accumulation curve. Here we develop the first statistically rigorous nonparametric method for estimating the minimum number of additional individuals, samples, or sampling area required to detect any arbitrary proportion (including 100%) of the estimated asymptotic species richness. The method uses the Chao1 and Chao2 nonparametric estimators of asymptotic richness, which are based on the frequencies of rare species in the original sampling data. To evaluate the performance of the proposed method, we randomly subsampled individuals or quadrats from two large biodiversity inventories (light trap captures of Lepidoptera in Great Britain and censuses of woody plants on Barro Colorado Island [BCI], Panama). The simulation results suggest that the method performs well but is slightly conservative for small sample sizes. Analyses of the BCI results suggest that the method is robust to nonindependence arising from small‐scale spatial aggregation of species occurrences. When the method was applied to seven published biodiversity data sets, the additional sampling effort necessary to capture all the estimated species ranged from 1.05 to 10.67 times the original sample (median ≈ 2.23). Substantially less effort is needed to detect 90% of the species (0.33–1.10 times the original effort; median ≈ 0.80). An Excel spreadsheet tool is provided for calculating necessary sampling effort for either abundance data or replicated incidence data.

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Drastic post‐LGM expansion and lack of historical genetic structure of a subtropical fig‐pollinating wasp ( Ceratosolen sp. 1) of Ficus septica in Taiwan - RONG‐CHIEN LIN; CAROL K‐L. YEUNG; SHOU‐HSIEN LI (Molecular Ecology, 2008)
The climatic oscillations of the last glacial period have had profound influences on the demography and levels of genetic diversity of extant species. Molecular evidence of glacial effects on temperate species has been well documented, whereas little is known regarding that on subtropical species. Here we present analyses based on partial sequences of the mitochondrial cytochrome c oxidase subunit I ( COI ) gene (1052 bp) and genotypes at 15 microsatellite loci to investigate the historical demography, population structure and ongoing gene flow of an undescribed fig‐pollinating wasp ( Ceratosolen sp. 1) of Ficus septica in subtropical Taiwan. Reconstructed historical demography based on the coalescent tree of COI sequences suggests that C . sp. 1 has undergone a drastic population expansion which was tightly coupled with climatic changes since the last glacial maximum (LGM). The magnitude of the population size change was approximately 500‐fold, indicating that the population of this wasp and its host was likely highly compressed during the last glacial period. The lack of significant population differentiation ( F ST F ST values) may be due to rapid postglacial expansion facilitated by long‐distance dispersal, although a low frequency of first‐generation migrants was detected. Our results clearly demonstrate how recent climatic changes since the LGM and dispersal ability have jointly shaped the genetic composition of a subtropical fig‐pollinating wasp.

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Selective Contrast Enhancement of Individual Alzheimer’s Disease Amyloid Plaques Using a Polyamine and Gd-DOTA Conjugated Antibody Fragment Against Fibrillar Aβ42 for Magnetic Resonance Molecular Imaging - Muthu Ramakrishnan; Thomas M. Wengenack; Karunya K. Kandimalla; Geoffry L. Curran; Emily J. Gilles; Marina Ramirez-Alvarado; Joseph Lin; Michael Garwood; Clifford R. Jack Jr.; Joseph F. Poduslo (Pharmaceutical Research, 2008)

DC-SIGN and L-SIGN: the SIGNs for infection - Ui-Soon Khoo; Kelvin Y. K. Chan; Vera S. F. Chan; C. L. Steve Lin (Journal of Molecular Medicine, 2008)

Characterization of novel microsatellite loci in the great leaf-nosed bat, Hipposideros armiger and cross-amplification in other related species - T. T. Guo; P. Y. Hua; L. K. Lin; S. Y. Zhang (Conservation Genetics, 2008)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Residential proximity to large airports and potential health impacts in New York State - S. Lin; J. P. Munsie; M. Herdt-Losavio; S. A. Hwang; K. Civerolo; K. McGarry; T. Gentile (International Archives of Occupational and Environmental Health, 2008)

Loss of apical monocilia on collecting duct principal cells impairs ATP secretion across the apical cell surface and ATP-dependent and flow-induced calcium signals - Michael B. Hovater; Dragos Olteanu; Elizabeth L. Hanson; Nai-Lin Cheng; Brian Siroky; Attila Fintha; Peter Komlosi; Wen Liu; Lisa M. Satlin; P. Darwin Bell; Bradley K. Yoder; Erik M. Schwiebert (Purinergic Signalling, 2008)

Treatment of polluted river water by a gravel contact oxidation system constructed under riverbed - D. F. Juang; W. P. Tsai; W. K. Liu; J. H. Lin (International Journal of Environmental Science and Technology, 2008)

Sensitivity of future ozone concentrations in the northeast USA to regional climate change - K. E. Kunkel; H.-C. Huang; X.-Z. Liang; J.-T. Lin; D. Wuebbles; Z. Tao; A. Williams; M. Caughey; J. Zhu; K. Hayhoe (Mitigation and Adaptation Strategies for Global Change, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

What are daily maximum and minimum temperatures in observed climatology? - X. Lin; K. G. Hubbard (International Journal of Climatology, 2008)

Detection of quantitative trait loci controlling extremely early heading in rice - Y. Nonoue; K. Fujino; Y. Hirayama; U. Yamanouchi; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2008)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Occupational exposure to ionizing and non-ionizing radiation and risk of non-Hodgkin lymphoma - Ken K. Karipidis; Geza Benke; Malcolm R. Sim; Timo Kauppinen; Anne Kricker; Ann Maree Hughes; Andrew E. Grulich; Claire M. Vajdic; John Kaldor; Bruce Armstrong; Lin Fritschi (International Archives of Occupational and Environmental Health, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

Mechanisms of reduced mitochondrial Ca2+ accumulation in failing hamster heart - Lin Lin; Virendra K. Sharma; Shey-Shing Sheu (Pflügers Archiv - European Journal of Physiology, 2007)

Soil Nutrient Load and Drain Water Quality in Seepage Fields Receiving Milk House Wastewater - S. Morin; J. K. Whalen; S. Barrington; X. Lin (Water, Air, & Soil Pollution, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

A dual site study of the rainwater chemistry within the Western Pacific region - K. M. Wai; S. H. Wang; P. A. Tanner; N. H. Lin (Journal of Atmospheric Chemistry, 2007)

Model-based ankle joint angle tracing by cuff electrode recordings of peroneal and tibial nerves - Chou-Ching K. Lin; Ming-Shaung Ju; Hang-Shing Cheng (Medical & Biological Engineering & Computing, 2007)

Spectrally segmented principal component analysis of hyperspectral imagery for mapping invasive plant species - F. Tsai; E.‐K. Lin; K. Yoshino (International Journal of Remote Sensing, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Analysis of extended HLA haplotypes in multiple sclerosis and narcolepsy families confirms a predisposing effect for the class I region in Tasmanian MS patients - Justin P. Rubio; Melanie Bahlo; Jim Stankovich; Rachel K. Burfoot; Laura J. Johnson; Stewart Huxtable; Helmut Butzkueven; Ling Lin; Bruce V. Taylor; Terence P. Speed; Trevor J. Kilpatrick; Emmanuel Mignot; et al. (Immunogenetics, 2007)

Characterizing the severe turbulence environments associated with commercial aviation accidents. A real-time turbulence model (RTTM) designed for the operational prediction of hazardous aviation turbulence environments - M. L. Kaplan; J. J. Charney; K. T. Waight; K. M. Lux; J. D. Cetola; A. W. Huffman; A. J. Riordan; S. D. Slusser; M. T. Kiefer; P. S. Suffern; Y.-L. Lin (Meteorology and Atmospheric Physics, 2006)

Pressure effect on the electronic structure of iron in (Mg,Fe)(Si,Al)O3 perovskite: a combined synchrotron Mössbauer and X-ray emission spectroscopy study up to 100 GPa - J. Li; W. Sturhahn; J. M. Jackson; V. V. Struzhkin; J. F. Lin; J. Zhao; H. K. Mao; G. Shen (Physics and Chemistry of Minerals, 2006)

Soil hydraulic manipulation and organic amendment for the enhancement of selenium volatilization in a soil–pickleweed system - B. Shrestha; S. Lipe; K. A. Johnson; T. Q. Zhang; W. Retzlaff; Z.-Q. Lin (Plant and Soil, 2006)

Mechanical Response of a Calcified Plaque Model to Fluid Shear Force - Tiantian C. Lin; Yin Tintut; Althea Lyman; Wendy Mack; Linda L. Demer; Tzung K. Hsiai (Annals of Biomedical Engineering, 2006)

High pressure elasticity and phase transformation in brucite, Mg(OH)2 - K. P. Jayachandran; Lin-gun Liu (Physics and Chemistry of Minerals, 2006)

Coordination between manganese and nitrogen within the ligands in the manganese complexes facilitates the reconstitution of the water-oxidizing complex in manganese-depleted photosystem II preparations - Shuqin Li; Guiying Chen; Guangye Han; Lin Ling; Deguang Huang; A. A. Khorobrykh; S. K. Zharmukhamedov; Qiutian Liu; V. V. Klimov; Tingyun Kuang (JBIC Journal of Biological Inorganic Chemistry, 2006)

Computational Simulations of the Human Magneto- and Electroenterogram - A. S. Lin; M. L. Buist; L. K. Cheng; N. P. Smith; A. J. Pullan (Annals of Biomedical Engineering, 2006)

Tissue Accumulation of Arsenic Compounds in Aquacultural and Wild Mullet (Mugil cephalus) - C.-W. Liu; K.-H. Lin; C.-S. Jang (Bulletin of Environmental Contamination and Toxicology, 2006)

Identification of elongation factor 1α as a potential associated binding partner for Akt2 - Janet Lau; Laura A. Castelli; Emme C. K. Lin; S. Lance Macaulay (Molecular and Cellular Biochemistry, 2006)

Organic Matter Stable Isotope (δ13C, δ15N) Response to Historical Eutrophication of Lake Taihu, China - Jinglu Wu; Lin Lin; Michael K. Gagan; Gerhard H. Schleser; Sumin Wang (Hydrobiologia, 2006)

Isolation and Characterization of Two Phenol-Degrading Yeast Strains from Marine Sediment - Z. Hu; Y. R. Wu; B. K. Lin; K. Maskaoui; D. H. Zhuang; T. L. Zheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Enhancement of chemosensitivity toward peplomycin by calpastatin-stabilized NF-κB p65 in esophageal carcinoma cells: possible involvement of Fas/Fas-L synergism - T.-L. Liu; H. Shimada; T. Ochiai; T. Shiratori; S.-E. Lin; M. Kitagawa; K. Harigaya; M. Maki; M. Oka; T. Abe; M. Takiguchi; T. Hiwasa (Apoptosis, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Additional microsatellite loci for the endangered St. Vincent Parrot, Amazona guildingii - M. A. Russello; K. Lin; G. Amato; A. Caccone (Conservation Genetics, 2006)

Weather and seasonal climate prediction for flood planning in the Yangtze River Basin - Zhaohui Lin; Jason K. Levy; Xingkui Xu; Sixiong Zhao; Jens Hartmann (Stochastic Environmental Research and Risk Assessment, 2005)

Risk Assessment of Arsenic Exposure from Consumption of Cultured Milkfish, Chanos chanos (Forsskål), from the Arsenic-Contaminated Area in Southwestern Taiwan - M.-C. Lin; H.-Y. Lin; H.-H. Cheng; Y.-C. Chen; C.-M. Liao; K.-T. Shao (Bulletin of Environmental Contamination and Toxicology, 2005)

Spatial Variations in Shear Stress in a 3-D Bifurcation Model at Low Reynolds Numbers - Mahsa Rouhanizadeh; Tiantian C. Lin; Diego Arcas; Juliana Hwang; Tzung K. Hsiai (Annals of Biomedical Engineering, 2005)

The Ratios of Individual Chemicals in a Mixture Determine the Degree of Joint Effect: The Climax Hypothesis - Z. Lin; Z. Ping; D. Kong; K. Yin; Z. Cai (Archives of Environmental Contamination and Toxicology, 2005)

Surface air temperature records biased by snow-covered surface - X. Lin; K. G. Hubbard; C. B. Baker (International Journal of Climatology, 2005)

Risk of non-Hodgkin lymphoma associated with occupational exposure to solvents, metals, organic dusts and PCBs (Australia) - Lin Fritschi; Geza Benke; Ann M. Hughes; Anne Kricker; Claire M. Vajdic; Andrew Grulich; Jennifer Turner; Samuel Milliken; John Kaldor; Bruce K. Armstrong (Cancer Causes & Control, 2005)

The nonlinear elasticity and related properties of anhydrous and hydrous γ-Mg2SiO4: a theoretical study - K. P. Jayachandran; Lin-gun Liu (Physics and Chemistry of Minerals, 2005)

Etoposide (VP-16) sensitizes p53-deficient human non-small cell lung cancer cells to caspase-7-mediated apoptosis - C.-C. Chiu; C.-H. M. Y. Lin; K. Fang (Apoptosis, 2005)

Characterizing the severe turbulence environments associated with commercial aviation accidents. Part 1: A 44-case study synoptic observational analyses - M. L. Kaplan; A. W. Huffman; K. M. Lux; J. J. Charney; A. J. Riordan; Y.-L. Lin (Meteorology and Atmospheric Physics, 2005)

Characterizing the severe turbulence environments associated with commercial aviation accidents. Part 2: Hydrostatic mesoscale numerical simulations of supergradient wind flow and streamwise ageostrophic frontogenesis - M. L. Kaplan; A. W. Huffman; K. M. Lux; J. D. Cetola; J. J. Charney; A. J. Riordan; Y.-L. Lin; K. T. Waight (Meteorology and Atmospheric Physics, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Fisheries of two tropical lagoons in Ghana, West Africa - H. R. Dankwa; J. M. Shenker; J. Lin; P. K. Ofori‐Danson; Y. Ntiamoa‐Baidu (Fisheries Management and Ecology, 2004)
The fisheries of two coastal lagoons, Keta and Songor, were studied as part of Ghana Coastal Wetlands Management Project (GCWMP) aimed at sustainable exploitation of wetland resources. Fish samples were obtained with seine nets and cast net as well as from local fishermen. Water quality parameters (pH, dissolved oxygen, temperature and turbidity) were similar in the two lagoons, except for salinity, which was significantly different ( P Sarotherodon melanotheron Rüppell, and the redchin tilapia, Tilapia guineensis (Bleeker), being the most important commercial fishes in both lagoons. The number of individuals for each species in Songor Lagoon were far more abundant, with densities several orders of magnitude higher than in Keta Lagoon. However, both species were significantly larger ( P S. melanotheron and T. guineensis respectively. Over‐fishing, use of small‐size mesh nets, limited mixing of marine and fresh water were some of the factors limiting fish production in both lagoons.

Adaptive processing bandwidth adjustment for laser Doppler flowmetry - Y. Y. Chen; Y. H. Lin; I. C. Jan; R. S. Liu; N. K. Chou; G. -J. Jan (Medical & Biological Engineering & Computing, 2004)

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.) - K. Fujino; H. Sekiguchi; T. Sato; H. Kiuchi; Y. Nonoue; Y. Takeuchi; T. Ando; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2004)

Calcium-antagonizing activity of S -petasin, a hypotensive sesquiterpene from Petasites formosanus , on inotropic and chronotropic responses in isolated rat atria and cardiac myocytes - Guei-Jane Wang; Jyh-Fei Liao; Kadon K. Hintz; Chuen-Chao Shi; Chieh-Fu Chen; Wen-Pin Chen; Ming-Jai Su; Yun-Lian Lin; Jun Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Nonlinear Time Series Analysis of Volcanic Tremor Events Recorded at Sangay Volcano, Ecuador - K. I. Konstantinou; C. H. Lin (Pure and Applied Geophysics, 2004)

Causes of spatial patterns of dead trees in forest fragments in Illinois - Y. Lin; Melissa L. Hulting; Carol K. Augspurger (Plant Ecology, 2004)

Efficacy and Safety of Cefotaxime in Combination with Metronidazole for Empirical Treatment of Brain Abscess in Clinical Practice: A Retrospective Study of 66 Consecutive Cases - A.-K. Jansson; P. Enblad; J. Sjlin (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Development of a Fragment Constant Method for Estimating the Mixture Toxicity - Z. Lin; L. Wang; P. Shi; D. Zhao; K. Yin (Archives of Environmental Contamination and Toxicology, 2004)

QSARs for Predicting the Toxicity of Mixtures Containing Polar Narcotic Chemicals - Z. Lin; K. Yin; C. Wu; L. Wang; H. Yu (Bulletin of Environmental Contamination and Toxicology, 2003)

Making thin polymeric materials, including fabrics, microbicidal and also water-repellent - Jian Lin; Shashi K. Murthy; Bradley D. Olsen; Karen K. Gleason; Alexander M. Klibanov (Biotechnology Letters, 2003)

Outbreaks of an iridovirus disease in maricultured large yellow croaker, Larimichthys crocea (Richardson), in China - X H Chen; K B Lin; X W Wang (Journal of Fish Diseases, 2003)

Strand Compositional Asymmetries of Nuclear DNA in Eukaryotes - Deng K. Niu; Kui Lin; Da-Yong Zhang (Journal of Molecular Evolution, 2003)

Nonrandom Intragenic Variations in Patterns of Codon Bias Implicate a Sequential Interplay Between Transitional Genetic Drift and Functional Amino Acid Selection - K. Lin; S. B. Tan; P. R. Kolatkar; R. J. Epstein (Journal of Molecular Evolution, 2003)

Operational Indicators for Measuring Agricultural Sustainability in Developing Countries - Lin Zhen; Jayant K. Routray (Environmental Management, 2003)

Tropical Glacier and Ice Core Evidence of Climate Change on Annual to Millennial Time Scales - Lonnie G. Thompson; Ellen Mosley-Thompson; M. E. Davis; P.-N. Lin; K. Henderson; T. A. Mashiotta (Climatic Change, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Selenium Removal from Irrigation Drainage Water Flowing Through Constructed Wetland Cells with Special Attention to Accumulation in Sediments - Suduan Gao; Kenneth K. Tanji; Douglas W. Peters; Zhiqing Lin; Norman Terry (Water, Air, & Soil Pollution, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Adsorption of Copper in the Different Sorbent/Water Ratios of Soil Systems - T. W. Chang; M. K. Wang; C. Lin (Water, Air, & Soil Pollution, 2002)

The cost of habitat selection in prairie voles: an empirical assessment using isodar analysis - Yu-Teh K. Lin; George O. Batzli (Evolutionary Ecology, 2002)

Allelic and locus heterogeneity in autosomal recessive gelatinous drop-like corneal dystrophy - Zhaoxia Ren; Pei-Yu Lin; Gordon K. Klintworth; Fumino Iwata; Francis L. Munier; Daniel F. Schorderet; Leila El Matri; Veena Theendakara; Surendra Basti; Madhukar Reddy; Fielding J. Hejtmancik (Human Genetics, 2002)

Mapping quantitative trait loci controlling seed longevity in rice (Oryza sativa L.) - K. Miura; S. Lin; M. Yano; T. Nagamine (Theoretical and Applied Genetics, 2002)

Structural Model of the Muscle Spindle - Chou-Ching K. Lin; Patrick E. Crago (Annals of Biomedical Engineering, 2002)

Neural and Mechanical Contributions to the Stretch Reflex: A Model Synthesis - Chou-Ching K. Lin; Patrick E. Crago (Annals of Biomedical Engineering, 2002)

The role of thiol compounds in increasing Agrobacterium-mediated transformation of soybean cotyledonary-node cells - P. Olhoft; K. Lin; J. Galbraith; N. Nielsen; D. Somers (Plant Cell Reports, 2001)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

Toward the mapping of physiological and agronomic characters on a rice function map: QTL analysis and comparison between QTLs and expressed sequence tags - K. Ishimaru; M. Yano; N. Aoki; K. Ono; T. Hirose; S. Y. Lin; L. Monna; T. Sasaki; R. Ohsugi (Theoretical and Applied Genetics, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Antibody responses to respiratory coronavirus infections of cattle during shipping fever pathogenesis - X. Q. Lin; K. L. O’Reilly; J. Storz; C. W. Purdy; R. W. Loan (Archives of Virology, 2000)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Photodegradation of the Herbicides Butachlor and Ronstar Using Natural Sunlight and Diethylamine - Y. J. Lin; C. Lin; K. J. Yeh; A. Lee (Bulletin of Environmental Contamination and Toxicology, 2000)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Agricultural Chemicals in the Alluvial Aquifer of a Typical County of the Arkansas Delta - H. S. Lin; H. D. Scott; K. F. Steele; H. I. Inyang (Environmental Monitoring and Assessment, 1999)

Soil Leaching Column Chromatographic Technique for Estimation of Leaching Behavior of Atrazine, Deethylatrazine, Deisopropylatrazine, and Hydroxyatrazine on Soil - F. Xu *, , X.-M. Liang; B. Lin; F. Su; H. Zhong; K.-W. Schramm; A. Kettrup (Bulletin of Environmental Contamination and Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Localizations of NS3 and E proteins in mouse brain infected with mutant strain of Japanese encephalitis virus - J. J. Wang; C. L. Liao; C. I. Yang; Y. L. Lin; C. T. Chiou; L. K. Chen (Archives of Virology, 1998)

Prediction of Water Solubility and Toxicity of Substituted Indoles to Photobacterium phosphoreum Using Molecular Connectivity Indices and Quantum Chemical Parameters - J. Dai; B. Sun; A. Zhang; K. Lin; L. Wang (Bulletin of Environmental Contamination and Toxicology, 1998)

Changes in nitric oxide synthase isoforms in the spinal cord of rat following induction of chronic arthritis - J. Wu; Q. Lin; Y. Lu; W. D. Willis; K. N. Westlund (Experimental Brain Research, 1998)

Pre- and Postnatal Exposure to 3,3',4,4'-Tetrachlorobiphenyl: II. Effects on the Reproductive Capacity and Fertilizing Ability of Eggs in Female Mice - A. Huang; S. Lin; R. Inglis; D. Powell; K. Chou (Archives of Environmental Contamination and Toxicology, 1998)

Transgenic peppermint ( Mentha × piperita L.) plants obtained by cocultivation with Agrobacterium tumefaciens - X. Niu; K. Lin; P. M. Hasegawa; R. A. Bressan; S. C. Weller (Plant Cell Reports, 1998)

Estimation of myocardial glucose utilisation with PET using the left ventricular time-activity curve as a non-invasive input function - X. Li; D. Feng; K. -P. Lin; S. -C. Huang (Medical & Biological Engineering & Computing, 1998)

αv Integrins mediate adhesion and migration of breast carcinoma cell lines - Nanette C. Wong; Barbara M. Mueller; Carlos F. Barbas; Pete Ruminski; Vito Quaranta; Emme C. K. Lin; Jeffrey W. Smith (Clinical & Experimental Metastasis, 1998)

Vapor Phase and Particulate Bound Polycyclic Aromatic Hydrocarbons in the Smoke of Mosquito Coils - J.-M. Lin; J.-K. Lee (Bulletin of Environmental Contamination and Toxicology, 1997)

Mapping quantitative trait loci associated with regeneration ability of seed callus in rice, Oryza sativa L. - F. Taguchi-Shiobara; S. Y. Lin; K. Tanno; T. Komatsuda; M. Yano; T. Sasaki; S. Oka (Theoretical and Applied Genetics, 1997)

Analysis of QTL×environment interaction for yield components and plant height in rice - J.-Y. Zhuang; H.-X. Lin; J. Lu; H.-R. Qian; S. Hittalmani; N. Huang; K.-L. Zheng (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Regulation of lipoprotein metabolism by estrogen in inbred strains of mice occurs primarily by posttranscriptional mechanisms - Rai Ajit K. Srivastava; Elaine S. Krul; Renee C. Lin; Gustav Schonfeld (Molecular and Cellular Biochemistry, 1997)

Structure and Stability of Non-Transform Discontinuities on the Mid-Atlantic Ridge between 24° N and 30° N - Sara Spencer; Deborah K. Smith; Johnson R. Cann; Jian Lin; Edward McAllister (Marine Geophysical Research, 1997)

Bcl-2 blocks peroxynitrite-induced apoptosis in HL-60 cells, an association with reactive oxygen species - K.-T. Lin; J.-Y. Xue; P. Y.-K. Wong (Inflammation Research, 1997)

Sweet potato (Ipomoea batatas) trypsin inhibitors expressed in transgenic tobacco plants confer resistance against Spodoptera litura - K.-W. Yeh; M.-I. Lin; S.-J. Tuan; Y.-M. Chen; C.-J. Lin; S.-S. Kao (Plant Cell Reports, 1997)

Sequence-based association analysis of HLA class I and II alleles in Japanese supports conservation of common haplotypes - K. Tokunaga; Yoshihide Ishikawa; Atsuko Ogawa; Huiru Wang; Shigeki Mitsunaga; Satoshi Moriyama; Ling Lin; Makoto Bannai; Yoshihisa Watanabe; Kouichi Kashiwase; Hidenori Tanaka; Tatsuya Akaza; et al. (Immunogenetics, 1997)

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

The epidemiology and surveillance of blood lead in Taiwan (R.O.C.): A report on the PRESS-BLL project - T.-N. Wu; Chen-Yang Shen; Saou-Hsing Liou; Guang-Yang Yang; K.-N. Ko; Show-Lin Chao; Chao-Chun Hsu; P.-Y. Chang (International Archives of Occupational and Environmental Health, 1997)

Assignment of DNA markers to Nicotiana sylvestris chromosomes using monosomic alien addition lines - D. F. Suen; C. K. Wang; R. F. Lin; Y. Y. Kao; F. M. Lee; C. C. Chen (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)

Identifying different types of de-differentiated microspores from indica-japonica F1 hybrids with subspecies-differentiating RFLP probes in rice - J. -H. Xie; M. -W. Gao; J. Lu; J. -Y. Zhuang; H. -X. Lin; H. -R. Qian; K. -L. Zheng (Theoretical and Applied Genetics, 1997)

Estimation of selected phenols in drinking water with In situ acetylation and study on the DNA damaging properties of polychlorinated phenols - Y.-J. Wang; J.-K. Lin (Archives of Environmental Contamination and Toxicology, 1995)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Electron microscopic evidence for the association of M 2 protein with the influenza virion - D. C. Jackson; Xi-Lin Tang; K. Gopal Murti; R. G. Webster; G. W. Tregear; W. J. Bean (Archives of Virology, 1991)

Typing of recent infectious bronchitis virus isolates causing nephritis in chicken - Z. Lin; A. Kato; Y. Kudou; K. Umeda; S. Ueda (Archives of Virology, 1991)

A parallel algorithm for estimating the secondary structure in ribonucleic acids - Y. Takefuji; C. W. Lin; K. C. Lee (Biological Cybernetics, 1990)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)

Mutants of Rhizobium japonicum defective in nodulation - Gary Stacey; Alan S. Paau; K. Dale Noel; Robert J. Maier; Lin E. Silver; Winston J. Brill (Archives of Microbiology, 1982)

Primary structure of the marmoset (Saguinus fuscicollis) hemoglobin. I. Use of tryptic maleylated peptides in the solubilization and sequence elucidation of the ?- and ?-chains - K. D. Lin; Y. K. Kim; A. I. Chernoff (Biochemical Genetics, 1976)

Synthesis of RNA with relation to aging inRhizoctonia solani - F. L. Davies; F. K. Lin; David Gottlieb (Archives of Microbiology, 1974)